Les obligations de la personne détenue dans les pays d’Afrique noire francophone : essai de systématisation - Kamnang Komguep, Irène Flore (Afrilex : Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2026)
L’agencement des obligations de la personne détenue dans de nombreux textes africains relatif au régime pénitentiaire manque de cohésion structurelle. En plus, certains de ces textes brillent par une imprécision et/ou par un silence notoire sur l’encadrement de certaines desdites obligations, ainsi que sur le régime des sanctions de leur violation. À ces écueils, s’ajoutent l’impact négatif des fléaux sociaux et économiques qui minent la plupart des États africains sur l’élan d’humanisation du statut des détenus. Il en découle la nécessité de cerner le contenu des obligations en question afin d’aboutir à leur classification cohérente et à l’appréciation de leur mise en œuvre à l’aune des exigences universelles liées au respect de la dignité humaine. Tel est l’enjeu de cet essai de systematisation des obligations de la personne détenue dans les États d’Afrique noire francophone. The arrangement of the obligations of detainees in many African texts relating to the penitentiary system lacks structural cohesion. Furthermore, some of these texts are notable for their imprecision and blatant silence regarding the regulation of certain of these obligations, as well as the system of sanctions for their violation. Adding to these obstacles is the negative impact of the social and economic ills plaguing most African states on the progress towards humanizing the status of detainees. This underscores the need to define the content of these obligations in order to arrive at a coherent classification and an assessment of their implementation in light of universal requirements related to respect for human dignity. This is the aim of this attempt to systematize the obligations of detainees in Francophone sub-Saharan African states.
Keywords: Detainees; Disciplinary regime; Duties; Lieu de détention; Obligations; Personne détenue; Place of detention; Régime disciplinaire; Violations

La promotion de l’accès à la justice au Mali : les modes de règlement des différends - Maiga, Mahamane Ibrahim (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2026)
L’article analyse comment la justice réparatrice et la médiation peuvent répondre plus efficacement aux conflits et violences au Sahel que le seul recours à l’enfermement et à la répression. Il met en regard les dispositifs formels (médiation pénale, médiation sociale encadrée par la norme AFNOR, Acte uniforme OHADA) et les mécanismes endogènes comme le cousinage à plaisanterie, les comités communautaires de résolution des conflits et d’autres pratiques coutumières au Mali et au Niger. En s’appuyant sur l’exemple rwandais des comités Abunzi, l’auteur montre l’intérêt mais aussi les limites d’une hybridation entre justice de proximité et encadrement étatique, notamment en termes de formation, de garanties procédurales et de risques d’instrumentalisation politique. Le texte articule ensuite les engagements normatifs (Accord pour la paix de 2015, Dialogue inter-maliens, CVJR) avec ces expériences de médiation pour souligner qu’une réconciliation durable exige des espaces de parole ancrés dans les communautés et reconnus par le droit. En conclusion, il plaide pour une politique publique de médiation qui combine normes régionales et nationales avec les ressources locales de paix, afin de restaurer la confiance envers l’État et prévenir durablement les conflits. This article examines how restorative justice and mediation can offer more effective responses to conflict and violence in the Sahel than purely repressive, incarceration-based approaches. It explores the interaction between formal mechanisms (criminal mediation, France’s social mediation norm AFNOR X60-600, and the OHADA Uniform Act on Mediation) and endogenous practices such as joking relationships, community dispute-resolution committees, and customary forums in Mali and Niger. Drawing on Rwanda’s Abunzi mediation system, the article highlights both the potential and the limits of hybridizing local justice with state regulation, particularly regarding training, procedural safeguards, and risks of political instrumentalization. It then links normative frameworks (the 2015 Algiers Peace Agreement, the 2024 Inter-Malian Dialogue recommendations, and the work of the Truth, Justice and Reconciliation Commission) with these mediation experiences to argue that sustainable reconciliation requires community-anchored, legally recognized spaces for dialogue. The article concludes that effective restorative justice in the Sahel depends on public policies that combine regional and national norms with local peace resources, in order to rebuild trust in the state and prevent conflict over the long term.
Keywords: Accès à la justice; Acte uniforme relatif à la médiation; Cousinage à plaisanterie (sanankuya); Droit OHADA; Justice réparatrice; Mali; Mediaccion; Mediation; Mécanismes coutumiers de résolution des conflits; Médiation pénale; Médiation sociale; Niger; Sahel

Le lot de copropriété à l’épreuve du droit ivoirien des biens - Sigui Seu, Xavier (Afrilex : Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2026)
Le lot de copropriété constitue l’unité fondamentale du régime de la copropriété immobilière en droit ivoirien. Issu du Code de la Construction et de l’Habitat de 2019, il se compose d’une partie privative et d’une quote-part de parties communes indissociables. Soumis à l’épreuve des catégories classiques du droit des biens (propriété, immeuble, droit réel, indivision), le lot de copropriété révèle une inadéquation profonde avec ces catégories héritées du Code civil, en raison de l’inconsistance matérielle de la partie privative et du particularisme de l’indivision forcée portant sur les parties communes. Cependant, cette inadéquation n’est pas le signe d’une anomalie irréductible : elle est le vecteur d’un renouvellement des catégories juridiques. Le lot, en tant qu’immeuble autonome par nature et objet d’un droit de propriété hybride, impose une relecture des notions de bien, de droit réel et de propriété, contribuant ainsi à l’évolution du droit des biens vers une plus grande abstraction et une plus grande plasticité. The condominium lot constitutes the fundamental unit of the condominium property regime under Ivorian law. Introduced by the 2019 Construction and Housing Code, it consists of a private unit and an inseparable share of common areas. When tested against the classical categories of property law — ownership, immovable property, real rights, co-ownership — the condominium lot reveals a deep inadequacy with the categories inherited from the Civil Code, owing to the material inconsistency of the private unit and the sui generis nature of the forced co-ownership over common areas. However, this inadequacy does not signal an irreducible anomaly: it is the vector of a renewal of legal categories. The lot, as an autonomous immovable by nature and the object of a hybrid property right, demands a rereading of the notions of property, real right, and ownership, thereby contributing to the evolution of property law towards greater abstraction and flexibility.
Keywords: 2019 Construction and Housing Code; Code de la Construction et de l’Habitat 2019; Condominium lot; Droit des biens; Droit ivoirien; Ivorian law; Lot de copropriété; Property law; Propriété immobilière; Real estate property

Le parcours juridique du jeu vidéo : étude de la chaîne de valeur d'une œuvre interactive - Guedj, Maxime (Université de Reims Champagne-Ardenne, 2026)
En sa qualité de divertissement le plus lucratif au monde, le jeu vidéo mérite une considération juridique à sa hauteur. Il n’est plus un simple jouet électronique, il est la pièce maitresse d’un secteur regroupant de multiples acteurs tels que les développeurs, les éditeurs, les distributeurs, les constructeurs, ainsi que les joueurs. Pour autant, malgré son importance économique, cette industrie a vu ses enjeux juridiques négligés par le législateur et les juges, laissant place à une insécurité juridique constante.L’étude de la chaîne de valeur du jeu vidéo, c’est-à-dire de l’ensemble des étapes allant de la création à la livraison du produit fini, présente en effet de nombreuses lacunes juridiques. Parmi elles figurent, par exemple, l’absence de statut juridique légal, la conclusion de contrats stipulant des clauses illicites, ou encore l’existence de marchés parallèles échappant au contrôle de l’éditeur.L'objectif de ces travaux consiste en une clarification des problématiques juridiques rencontrées par les acteurs de cette industrie. À cet éclaircissement s'ajoute la proposition de solutions qui sont soit issues du droit positif français et européen, soit inspirées des autres droits nationaux, soit totalement nouvelles. La production et la commercialisation d'un jeu vidéo sont loin d'être une promenade de santé, il s'agit, au contraire, d'un véritable parcours juridique. As the world’s most lucrative form of entertainment, the video game industry deserves legal consideration commensurate with its stature. It is no longer merely an electronic toy; it is the cornerstone of a sector comprising a wide range of stakeholders, including developers, publishers, distributors, manufacturers, and players. However, despite its economic importance, this industry has seen its legal issues neglected by lawmakers and judges, leading to constant legal uncertainty.An examination of the video game value chain—that is, all the stages from creation to delivery of the finished product—reveals numerous legal gaps. These include, for example, the lack of a legal status, the conclusion of contracts containing unlawful clauses, and the existence of parallel markets beyond the publisher’s control.The objective of this work is to clarify the legal issues faced by industry stakeholders. In addition to this clarification, the study proposes solutions that are either derived from French and European positive law, inspired by other national legal systems, or entirely new.The production and marketing of a video game are far from a walk in the park, on the contrary, it is a veritable legal pathway.
Keywords: Commercialisation; Industrie et commerce; Jeu vidéo; Marketing; Parcours; Pathway; Production; Video game; Video games

Restriction des transactions de devises en espèce et effet potentiel sur le pouvoir d’achat des ménages : cas de la RDC - Mavuma, David; Kahambwe, Chris (MPRA Paper, 2026)
Cette étude analyse les effets potentiels des coûts de transaction liés aux paiements électroniques en devises sur le pouvoir d’achat des ménages en République Démocratique du Congo dans le cadre de la réforme envisagée par la Banque Centrale du Congo. À partir d’une approche fondée sur l’analyse des coûts de transaction et la simulation des tarifs appliqués par les principaux opérateurs de Mobile Money, les résultats montrent que les frais de transaction peuvent accroître le coût effectif des biens et services et réduire le pouvoir d’achat des consommateurs. Dans un contexte marqué par la pauvreté, la faible bancarisation et l’importance du secteur informel, l’étude souligne la nécessité d’accompagner la réforme par des mesures d’encadrement et d’inclusion afin de préserver le bien-être des populations vulnérables et de garantir l’atteinte des objectifs de traçabilité financière. This study examines the potential effects of transaction costs associated with electronic payments in foreign currency on household purchasing power in the Democratic Republic of the Congo within the framework of the reform proposed by the Central Bank of Congo. Using a transaction cost analysis and simulations based on the tariff structures of major Mobile Money operators, the findings suggest that transaction fees may increase the effective cost of goods and services and reduce consumers’ purchasing power. In a context characterized by poverty, low banking penetration, and a large informal sector, the study highlights the need for appropriate regulatory and inclusion measures to protect vulnerable populations and ensure the achievement of the reform’s financial traceability objectives.
Keywords: Coûts de transaction; Democratic Republic of Congo; Financial Inclusion; Inclusion financière; Mobile Money; Payment Reform; Pouvoir d’achat; Purchasing Power; RDC; Réforme des paiements; Transaction Costs

Du citoyen en arme défenseur des libertés au juge garant de l'état de droit - Nerrant, Stéphane (Normandie Université, 2026)
L’arme et son statut juridique et social au sein des sociétés ont connu une large évolution depuis l’origine de la civilisation, puisque l’on est progressivement passé d’un principe de liberté de port et de détention à une interdiction plus ou moins stricte. Ainsi, la réglementation des armes est avant tout pour chaque pays un produit de l’histoire, elle traduit aussi une conception idéologique, celle du rôle de l’Etat face aux libertés individuelles, mettant en tension les enjeux d’une part, de sécurité publique avec ceux d’un droit personnel à défendre sa vie au moyen d’une arme, et d’autre part, de défense nationale avec ceux d'un devoir collectif de défendre le pays grâce à une masse de citoyens entrainés au maniement des armes et formant l'armée.C’est pourquoi, les révolutionnaires de 1789 ont rangé le droit d’avoir une arme parmi les droits civiques et qu’ils avaient envisagé d’inscrire ce droit dans la DDHC dans la mesure où la possession d'armes a longtemps fait la distinction entre l'homme libre et l'esclave. A ce titre, même si désormais, la légitimité émane des citoyens puisqu’en principe le pouvoir exécutif n’est que le « ministre du souverain qu’est le peuple ». Force est de constater que la citoyenneté et les droits naturels ne sont pas le fruit d’un contrat social voulu par l’Etat issu de l’état de droit, ils sont le résultat d’un rapport de force par lequel le citoyen est parvenu à s’extraire de sa position de sujet pour revendiquer sa liberté en contrepartie de ses prestations fiscales et militaires.Toutefois, force est de constater que le droit positif actuel dans ce domaine est devenu de plus en plus restrictif en raison notamment de la prévalence d’une vision sécuritaire de la société consistant à limiter l’usage et la connaissance des armes, voire inculquer une peur de l’armement qui conduit à un déséquilibre liberticide entre un Etat se réservant le monopole de l’usage des armes et les citoyens dépossédés de leur droit fondamental à assurer par ce moyen leur propre défense, résister à l’oppression voire participer eux-mêmes au respect de l’ordre public, ainsi que de la défense du pays et de ses institutions démocratiques. Ce régime juridique des armes révèle aussi l’abandon d’un modèle fondé sur la souveraineté du peuple pour un modèle de contrôle étatique comportant un risque de dérive autoritaire, les violences armées demeurant par ailleurs essentiellement le fait des Etats et non des individus. D’autant plus que le droit français, marginalise le législateur au profit de l’administration qui surclasse systématiquement les armes et met en place un système de fichage centralisé dangereux pour les libertés individuelles dans un contexte de droit international enclin au désarmement des populations. De ce point de vue, la question du « monopole de la violence physique légitime » dans une démocratie où le peuple est souverain est centrale au regard du faible nombre d’homicides par armes à feu et de l’absence de menace réelles qu’elles représentent entre les mains des honnêtes gens. C’est pourquoi, une réglementation plus fine serait intéressante car de nature à rétablir une forme d'égalité entre le fort et le faible ou entre l’honnête citoyen et le criminel. The legal and social status of firearms within societies has undergone significant evolution since the dawn of civilization, as we have gradually moved from the principle of freedom to carry and possess them to a more or less strict prohibition. Thus, firearms regulations are, above all, a product of history for each country; they also reflect an ideological conception, that of the role of the State in relation to individual liberties. This creates tension between the issues of public safety and the personal right to defend one's life with a firearm, and between national defense and the collective duty to defend the country through a mass of citizens trained in the use of weapons and forming the army.This is why the revolutionaries of 1789 included the right to bear arms among civic rights and considered enshrining this right in the Declaration of the Rights of Man and of the Citizen, given that the possession of weapons had long distinguished between free men and slaves. In this respect, even though legitimacy now emanates from the citizens, since in principle the executive power is merely the ''minister of the sovereign, which is the people,'' it must be acknowledged that citizenship and natural rights are not the product of a social contract established by the State based on the rule of law; they are the result of a power dynamic through which the citizen has managed to transcend their position as a subject to claim their freedom in exchange for their tax and military contributions.However, it must be acknowledged that current positive law in this area has become increasingly restrictive, due in particular to the prevalence of a security-focused vision of society that limits the use and knowledge of weapons, even instilling a fear of arms. This leads to a liberty-destroying imbalance between a state that reserves for itself the monopoly on the use of weapons and citizens deprived of their fundamental right to ensure their own defense, resist oppression, and even participate in maintaining public order, as well as defending the country and its democratic institutions. This legal regime governing weapons also reveals the abandonment of a model based on popular sovereignty in favor of a model of state control that carries a risk of authoritarian drift, since armed violence remains primarily the work of states and not individuals.This is all the more relevant given that French law marginalizes the legislature in favor of the administration, which systematically prioritizes firearms and implements a centralized surveillance system that is dangerous for individual liberties, particularly in a context of international law that tends toward the disarmament of populations. From this perspective, the question of the ''monopoly on legitimate physical violence'' in a democracy where the people are sovereign is central, considering the low number of homicides by firearms and the absence of any real threat they pose in the hands of law-abiding citizens. Therefore, more nuanced regulations would be beneficial, as they could help restore a form of equality between the strong and the weak, or between the law-abiding citizen and the criminal.
Keywords: Arme à feu; Arme à feu (acquisition); Arme à feu (détention); Arme à feu (port); Armes à feu (contrôle); Armée; Chasse; Citoyenneté; Civis et miles; Contrat social; Directive européenne; Douane; Droit civique; Droit naturel; Droit positif; Droit pénal; Droit à la vie; Droits aux armes; Droits aux loisirs; Démocratie; Garde nationale; Hoplophobe; Interdiction progressive; Jurisprudence; Justice; Liberté; Législateur; Légitime défense; Matériel de guerre; Motif légitime; Peur des armes; Police; Primauté du droit; Propriété; Recrutement et engagement; Réglementation; Résistance politique; Résistance à l'oppression; Saisie sans indemnité; Service militaire; Souveraineté; Surclassement des armes; Sécurité; Sûreté; Tir sportif; État de droit; Évolution historique

La formation du contrat électronique : dispositif légal (répressif) de protection du cyberconsommateur et modes alternatifs de règlement des conflits (M.A.R.C.) - Diallo, Boubacary (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2026)
L’objectif principal de cette étude est de révéler le dispositif légal répressif de protection du cyberconsommateur. Les résultats de cette étude montrent que le législateur malien, communautaire, sous régional et régional y compris, ont misé beaucoup sur la protection des cyberconsommateurs, en adoptant une politique qui s’articule principalement sur la confidentialité, la protection de la vie privée, la protection de la propriété intellectuelle, et le règlement des conflits par les modes alternatifs de règlement des conflits (M.A.R.C.) déclenchés entre les différentes parties de la transaction en ligne.
Keywords: Contrat électronique; Cyberconsommation; E-commerce; MARC; Règlement des conflits

La légitime défense en droit pénal - Traoré, Amadou Tidiane (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2026)
La légitime défense est une cause d'exonération fondamental en droit pénal, qui autorise une personne à repousser une attaque injustifiée par une riposte proportionnée, sans encourir de sanction pénale. Cette institution juridique incarne, dans sa finalité, la protection de l'individu et la préservation de la société contre les actes d'agression injustifiés. Elle est donc une manifestation du droit naturel, puisque le droit de se défendre contre une attaque injuste est reconnu par tous les systèmes juridiques, anciens comme modernes. Toutefois, cette justification ne saurait être admise qu'à certaines conditions strictement encadrées par la loi, dans le but de prévenir les abus et de garantir le respect de l'ordre public. La légitime défense ne saurait être invoquée de manière arbitraire, car elle constitue une dérogation exceptionnelle au principe de la responsabilité pénale. En l'absence de ces conditions, l'auteur d'un acte violent ne pourrait se prévaloir de ce mécanisme pour échapper à une sanction pénale. Elle constitue une cause d'irresponsabilité pénale totale, permettant à l'auteur d'un acte autrement repréhensible d'échapper à toute peine, dès lors que les conditions strictes de la loi sont réunies. Elle répond à une logique de nécessité et d'exception, dans laquelle la riposte n'est admise que pour prévenir un danger immédiat, réel et injuste. Mais cette exonération ne saurait être automatique : encore faut-il établir la réalité de la menace, la proportionnalité de la défense et son caractère immédiat, ce qui pose inévitablement la question de la charge de la preuve et des mécanismes présomptifs que la loi peut instituer. Self-defense is a fundamental ground for exemption in criminal law, allowing a person to repel an unjustified attack with a proportionate response, without incurring criminal penalty. This legal institution embodies, in its purpose, the protection of the individual and the preservation of society against unjustified acts of aggression. It is therefore a manifestation of natural law, since the right to defend oneself against an unjust attack is recognized by all legal systems, both ancient and modern. However, this justification can only be admitted under certain conditions strictly defined by law, in order to prevent abuses and guarantee respect for public order. Self-defense cannot be invoked arbitrarily, as it constitutes an exceptional exception to the principle of criminal responsibility. In the absence of these conditions, the perpetrator of a violent act could not rely on this mechanism to escape criminal punishment. It constitutes a ground for total criminal irresponsibility, allowing the perpetrator of an otherwise reprehensible act to escape all punishment, provided the strict conditions of the law are met. It responds to a logic of necessity and exception, in which retaliation is only permitted to prevent an immediate, real, and unjust danger. However, this exemption cannot be automatic: it is still necessary to establish the reality of the threat, the proportionality of the defense, and its immediate nature, which inevitably raises the question of the burden of proof and the presumptive mechanisms that the law may establish.
Keywords: Agression injustifiée; Criminal irresponsibility; Danger immédiat; Danger réel et injuste; Immediate danger; Irresponsabilité pénale; Légitime défense; Real and unjust danger; Retaliation; Riposte; Self-defense; Unjustified aggression

Le recouvrement forcé des dettes des personnes morales de droit public au Cameroun - Akamesse, Marie Antoinette (Afrilex : Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2026)
L’activité économique demeure largement conditionnée par le crédit dans tout système de libéralisme juridique. Cette activité ne peut valablement être promue que dans un cadre favorable au climat des affaires et par conséquent attractif aux investisseurs et financiers nationaux et internationaux. C’est ainsi que législateur OHADA ayant pour objectif principal la protection des créanciers à travers l’instauration d’une sécurité judiciaire et juridique dans son espace, va prévoir en absence des moyens volontaires, les voies d’exécution forcée sur le patrimoine de tout débiteur. C’est-à-dire des moyens légaux aménagés pour contraindre des personnes à s’exécuter contre leur gré. Qui, au plus grand désarrois, ne s’appliquent pas à toutes les personnes, dont, les personnes morales de droit public qui jouissent de l’immunité d’exécution, prérogative de protection de la puissance publique contre toute forme d’aliénations forcées. Toutefois, avec le nouvel acte uniforme OHADA, ce bouclier semble trouver des moyens de contournement. Ce qui pourrait amener à se demander si l’on peut contraindre les débiteurs souverains à payer leurs dettes à la suite de ce nouvel acte. A l’analyse de la thématique à travers l’exégèse des textes juridiques et de la jurisprudence on se permet d’affirmer l’exiguë de cette procédure. Une restriction qui se justifie par la paralysie des moyens juridiques de droit commun toute en laissant une possibilité de contrainte par voies d’exception. Economic activity remains largely dependent on credit in any system of legal liberalism. This activity can only be effectively promoted in a framework that is conducive to a favorable business climate and therefore attractive to national and international investors and financiers. Thus, OHADA legislators, whose main objective is to protect creditors by establishing judicial and legal security within its jurisdiction, will provide for enforcement measures against the assets of any debtor in the absence of voluntary measures. These are legal means designed to compel individuals to comply against their will. Conversely, legal entities governed by public law enjoy immunity from enforcement, a prerogative of protection of public authority against any form of forced alienation. This shield has been somewhat circumvented by the new OHADA Uniform Act. This could lead to the question of whether sovereign debtors can be compelled to pay their debts as a result of this new act. After analyzing the issue through the exegesis of legal texts and case law, we can affirm the limited nature of this procedure. This restriction is justified by the paralysis of the legal means available under ordinary law, while leaving open the possibility of payment by way of exception.
Keywords: Compulsory collection; Dette publique; Immunity from enforcement; Immunité d’exécution; Legal entities governed by public law; Personne morale de droit public; Public debt; Recouvrement forcé

La souscription à un emprunt obligataire : aspects juridiques - Balla Ondoua, Jean Olivier (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2026)
La contribution des banques et des institutions financières internationales au budget des pays en voies de développement demeure conséquente. Seulement, il faut le dire, tant le crédit octroyé au travers des banques que l’aide au développement qui y est délivré par le truchement des accords de prêts, n’ont alors jusqu’à date, pas véritablement su s’adapter au contexte social africain. C’est sans doute ce qui justifie l’alternative que propose désormais la finance directe sur le marché financier au moyen de l’emprunt obligataire. En effet, comparativement aux conditionnalités de prêts aigues qu’imposent les banques et les institutions financières internationales que sont la BM et le FMI, l’emprunt au bénéfice du budget de l’Etat par émission des valeurs du Trésor, pose simplement le principe de sa libre accessibilité à tous les ressortissants CEMAC. En revanche, il est porté un ensemble d’obligations au compte de l’Etat débiteur qui organise et veille tours à tour à la conception, l’exécution, au fonctionnement et la bonne fin de l’opération vis-à-vis des différents investisseurs qui souscrivent à l’appel public à l’épargne lancé par lui. Le présent article vise donc à mettre en exergue les différents aspects juridiques liés aux conditions de souscription des adhérents de l’Etat émetteur, des ressortissants CEMAC et même, des investisseurs non ressortissants CEMAC. Dans ce dernier cas de figure, il importe de rappeler dans cette analyse, ce que prévoit le droit positif Camerounais pour ce qui est de la souscription des Obligations du Trésor Assimilables tant par les résidents CEMAC et non-résidents d’une part et l’attrait qu’elle exerce en matière de recette budgétaire aux vues des transactions en monnaie locale et autres actions en convertibilité des devises qu’une telle opération génère d’autre part. The contribution of banks and international financial institutions to the budget of developing countries remains significant. However, it must be said that both the credit granted through banks and the developments have not, to date, truly adapted to the African social context. This is probably what justifies the alternative now proposed by direct finance on the financial market through bond issuance. Indeed, compared to the stringent loan conditions imposed by banks and international financial institutions such as the World Bank and the International Monetary Fund, Borrowing for the benefit of the state budget through the issuance of Treasury securities simply establishes the principle of its free accessibility to all CEMAC nationals. On the other hand, a set of obligations is imposed on the debtor state, which organizes ensures the design, execution, operation, and successful completion of the operation with respect to the public call for saving launched by it. This article therefore aims to highlight the various legal aspects related to the subscription conditions of the issuer state’s members, CEMAC nationals, and even non-CEMAC investors. In the latter case, it is important to recall in this analysis what Cameroonian positive law provides for regarding the subscription of assimilable treasury bond by both CEMAC residents and non-residents, on the one hand, and the appeal it generates in terms of budget revenue in view of local currency actions that such an operation generates, on the other hand.
Keywords: Alternative d’endettement; Autonomie financière; Budgetary sovereignty; Debt alternative; Dette; Direct financing; Financement Directe; Financial autonomy; Souveraineté budgétaire

De la protection du locataire à la sauvegarde des intérêts du bailleur : étude de l’équilibre contractuel du bail d’habitation au Cameroun - Dongmo Donfack, Joël Fabrice (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
L’étude de l’équilibre contractuel du bail d’habitation au Cameroun conduit naturellement, ou presque, à l’analyse des tensions structurelles qui traversent le régime juridique du bail d’habitation, pris entre l’exigence de justice sociale et la nécessité de préserver les intérêts légitimes du bailleur. Cette démarche suscite le questionnement central qui porte sur la capacité du droit positif camerounais à instaurer un équilibre contractuel effectif dans un contexte marqué par une asymétrie normative en faveur du locataire. S’appuyant sur l’examen des textes applicables au bail d’habitation, éclairé par la pratique contractuelle et le contentieux locatif ainsi que par les apports de la doctrine il s’agit d’évaluer la cohérence du dispositif normatif au regard des principes contemporains du droit des contrats et de la notion d’équilibre contractuel. Est ainsi mis en évidence la socialisation du bail d’habitation fondée sur la protection du locataire qui a conduit à une marginalisation progressive des prérogatives du bailleur, marginalisation génératrice d’insécurité juridique et de dysfonctionnements pratiques. Toutefois, cette asymétrie pourrait ne pas passer survivre à une justice contractuelle rénovée, reposant sur une redéfinition encadrée de l’autonomie de la volonté et sur l’élaboration d’un modèle contractuel du bail d’habitation conciliant protection sociale et sécurité juridique. L’équilibre contractuel apparaît alors comme un processus dynamique au service de la stabilité du marché locatif camerounais. An examination of the contractual balance in residential leases in Cameroon naturally— or almost naturally—leads to an analysis of the structural tensions within the legal framework governing residential leases, which is caught between the demand for social justice and the need to protect the legitimate interests of the landlord. This approach raises the central question of whether Cameroonian positive law is capable of establishing an effective contractual balance in a context marked by a normative asymmetry in favor of the tenant. Drawing on an examination of the laws applicable to residential leases, informed by contractual practice and rental litigation as well as by contributions from legal scholarship, the aim is to assess the coherence of the legal framework in light of contemporary principles of contract law and the concept of contractual balance. This highlights the socialization of residential leases based on tenant protection, which has led to a gradual marginalization of the landlord’s rights—a marginalization that generates legal uncertainty and practical dysfunctions. However, this imbalance may not survive a reformed contract law system based on a carefully defined redefinition of contractual freedom and the development of a residential lease model that balances social protection and legal certainty. Contractual balance thus emerges as a dynamic process that promotes stability in Cameroon’s rental market.
Keywords: Bail d’habitation; Cameroonian law; Contractual balance; Contractual justice; Droit camerounais; Intérêts du bailleur; Justice contractuelle; Landlord’s interests; Protection du locataire; Residential lease; Tenant protection; Équilibre contractuel

Le chômage des jeunes diplômés au Mali : entre besoins d’implication du milieu socioprofessionnel et réforme du système de formation - Fomba, Mamadou (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2026)
Au Mali, les questions de l’emploi des jeunes en général et celles des jeunes diplômés en particulier, sont devenues préoccupantes. Dans le présent article, nous nous proposons d’apporter notre modeste contribution à ces questions à travers nos réflexions dont les fruits nous ont conduits vers deux leviers qu’il faut actionner en même temps : la connexion de la formation avec le milieu socio-professionnel et la réforme en profondeur du système éducatif et de formation. Cela revient à lier la formation avec les besoins du secteur privé, principal pourvoyeur d’emplois, mais aussi à adosser la formation aux organismes de formation qu’il faut restructurer. Il faut, aussi, faire la refonte du système éducatif en le rendant plus professionnalisant à travers l’existence de centres de formation professionnelle et technique et en créant en son sein une Agence dédiée à la reconversion des jeunes diplômés dans un contexte d’inadéquation emploi/formation et/ou mal formés et disponibles sur le marché de l’emploi.
Keywords: Chômage; Formation; Insertion; Jeune diplômé; Mali; Reconversion

Approche critique du mécanisme de règlement des différends commerciaux devant la CCI - Kesse, Julia Sainte-Colombe (Université de Montréal, 2026)
Cette étude analyse de manière critique le mécanisme de résolution des litiges commerciaux de la Chambre de commerce internationale (CCI) en trois étapes : précontentieux, contentieux et post contentieux. Il examine d’abord l’évolution des méthodes amiables telles que la médiation, la conciliation ou les commissions de règlement des différends mises en œuvre par la CPI pour la prévention des conflits. Ensuite, la validité, les conditions de validité et les conditions applicables de la procédure d'arbitrage sont analysées. Enfin, elle se penche sur la question de la contestation de l'exécution du jugement, notamment par le biais de la Convention de New York. Cet ouvrage met en lumière les apports et les lacunes du système, en insistant sur les différences sectorielles, les résistances culturelles (en Afrique) et les défis de légitimation. L’on a conclu qu’il était nécessaire de renforcer la complémentarité entre le règlement amiable et l’arbitrage afin d’établir une justice commerciale plus efficace, universelle et durable. This thesis critically analyses the International Chamber of Commerce (ICC) mechanism for resolving commercial disputes at three stages: pre-dispute, dispute and post-dispute. First, it examines the development of amicable procedures such as mediation, arbitration or dispute settlement bodies adopted by the ICC to prevent conflicts. It then analyses the effectiveness of arbitration proceedings, the conditions for their entry into force and the elements for their applicability. Finally, it questions the enforcement of arbitration awards, especially under the New York Convention. The study highlights the strengths and weaknesses of the system, underlining sectoral differences, cultural resistance (in Africa and Asia) and legitimacy challenges. It concludes that in order to build a more effective, universal and sustainable commercial justice system, it is necessary to strengthen the complementarity between amicable settlement and arbitration.
Keywords: Alternative; Arbitrage commercial international; Chambre de commerce internationale; Commercial litigation; Contentieux commercial; Convention de New York (1958); Enforcement of arbitral awards; Exécution des sentences arbitrales; International Chamber of Commerce (ICC); International commercial arbitration; International commercial mediation; Médiation commerciale internationale; New York Convention

Droit des biens et intuitus personae - Lai, Alexia (Université de Bordeaux, 2026)
Le droit des biens demeure marqué par l’absence d’une analyse pleinement satisfaisante de l’insertion de la considération de la personne en son sein. Ni les tentatives d’identification de biens à caractère personnel ni les entreprises de classification correspondantes ne permettent de rendre compte, de manière cohérente, des difficultés rencontrées. Cette situation révèle la nécessité d’un outil conceptuel apte à appréhender globalement le phénomène et à en expliquer la logique. L’étude propose, à cette fin, de mobiliser le concept d’intuitus personae, en reprenant ses fondements issus du droit des contrats et en les adaptant au droit des biens, tout en élargissant sa définition à l’expression du respect dû à la personne humaine. Grâce à sa plasticité et à l’intensité variable de la considération qu’il exprime, il constitue un outil d’analyse fécond pour le droit des biens, permettant de dépasser une approche strictement classificatoire. L’intuitus personae révèle ainsi la complexité de la patrimonialité, qui s’exprime en degrés selon l’intensité de la considération de la personne. Une telle perspective permet non seulement de décrire ces mécanismes, mais également de résoudre certaines difficultés de qualification et d’envisager une amélioration des régimes existants. French property law remains characterized by the lack of a fully satisfactory analysis regarding the integration of the consideration of the person within its sphere. Neither the attempts to identify “property of a personal nature” nor the related classification efforts have succeeded in providing a coherent account of the challenges encountered. This state of affairs underscores the need for a conceptual tool capable of apprehending the phenomenon as a whole and explaining its underlying logic. To this end, the present study proposes to mobilize the concept of intuitus personae, drawing upon its foundations in contract law and adapting them to property law, while expanding its definition to encompass the respect due to the human person. Owing to its plasticity and the variable intensity of the consideration it conveys, it serves as a fruitful analytical tool for property law, making it possible to move beyond a strictly classificatory approach. Intuitus personae thus reveals the complexity of patrimonality, which is expressed in degrees depending on the intensity of the consideration of the person. Such a perspective allows not only for the description of these mechanisms but also for the resolution of certain characterization difficulties and the proposal of improvements for existing legal frameworks.
Keywords: Bien; Biens (droit); Cession; Contrats; Droit des biens; Intuitus personae; Ownership; Patrimoine; Patrimony; Property; Property law; Propriété

Les obstacles à l’accès à la justice au Mali - Maiga, Mahamane Ibrahim (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2026)
Cet article analyse les obstacles sociaux et économiques entravant l’accès à la justice au Mali, où 86% de la population vit en situation de pauvreté cela est dû à une crise multidimensionnelle et multi forme que connaît le Mali depuis une decennie. Les barrières sociales incluent l’analphabétisme, qui favorise la méconnaissance des lois modernes – notamment en matière de documentation civile, baux fonciers et autres, exposant les justiciables à des expulsions arbitraires malgré leurs investissements – ainsi que les tensions avec la police judiciaire, perçue comme arrogante et rackettrice, ce qui décourage le dépôt de plaintes formelles (7% seulement de recours aux tribunaux). Les freins économiques résultent de coûts prohibitifs (avocats, huissiers, déplacements), d’une aide juridictionnelle sous financée et d’une corruption systémique imposant des pots-de-vin quotidiens, transformant la justice en un privilège élitiste. Les interactions croisées de ces obstacles perpétuent l’impunité, une « justice à deux vitesses » et un recours massif aux justices informelles (93% des litiges), fragilisant l’État de droit depuis 2012. Des réformes urgentes, campagnes de sensibilisation juridique, renforcement des contrats écrits, formation des agents de police et lutte anticorruption – s’imposent pour une inclusion effective des populations vulnérables, particulièrement les femmes et les habitants des zones rurales. This article analyzes the social and economic obstacles hindering access to justice in Mali, where 86% of the population lives in multidimensional poverty. Social barriers include illiteracy, which fosters ignorance of modern laws—particularly in matters of land leases, exposing litigants to arbitrary evictions despite their investments—as well as tense relations with the judicial police, perceived as arrogant and extortive, which discourages formal complaints (only 7% of disputes reach the courts). Economic barriers stem from prohibitive costs (lawyers, bailiffs, travel), underfunded legal aid, and systemic corruption involving daily bribes, turning justice into an elite privilege. The interplay of these obstacles perpetuates impunity, a “two-tier” justice system, and heavy reliance on informal justice (93% of disputes), thereby undermining the rule of law since 2012. Urgent reforms—legal awareness campaigns, strengthened written contracts, improved police training, and robust anti-corruption measures—are essential to effectively include vulnerable groups, especially women and rural populations.
Keywords: Accès à la justice; Analphabétisme; Barrières économiques; Corruption judiciaire; Obstacles sociaux; Pauvreté multidimensionnelle; Police judiciaire

La souveraineté économique et le rôle de l’État dans l’encadrement des investissements étrangers en République centrafricaine - Ngamana, Evariste (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
En République centrafricaine, la souveraineté économique repose sur la capacité de l’État à encadrer et orienter les investissements étrangers tout en préservant ses intérêts nationaux. L’État définit les règles juridiques et institutionnelles qui garantissent la transparence, la sécurité et l’équité dans les relations avec les investisseurs. Il protège les investissements contre l’expropriation arbitraire et la discrimination, tout en favorisant l’égalité de traitement entre investisseurs nationaux et étrangers. D’abord, les capitaux étrangers doivent contribuer au développement durable par la création d’emplois, le transfert de compétences et le financement d’infrastructures essentielles. En ce sens, l’État centrafricain encadre aussi la libre circulation des investisseurs. Il assure la protection de leurs biens et familles, ainsi que leur droit de transférer librement les revenus issus des investissements à l’étrangers. Ce rôle régulateur évite les abus, renforce la confiance des partenaires internationaux et consolide la stabilité économique. Ensuite, en exerçant sa souveraineté, l’État centrafricain cherche à concilier l’ouverture aux capitaux étrangers et l’autonomie décisionnelle. Il s’agit d’un équilibre délicat entre attractivité et protection des investissements. Ces objectifs visent à transformer les capitaux étrangers en leviers de croissance inclusive. Enfin, cette démarche améliore l’image du pays. Elle renforce son intégration régionale et promeut une gouvernance économique responsable en vue d’un développement harmonieux et durable. In the Central African Republic, economic sovereignty rests on the State’s ability to regulate and guide foreign investments while safeguarding national interests. The State establishes legal and institutional frameworks that ensure transparency, security, and fairness in relations with investors. It protects investments against arbitrary expropriation and discrimination, while promoting equal treatment between domestic and foreign investors. First, foreign capital must contribute to sustainable development through job creation, skills transfer, and the financing of essential infrastructure. In this regard, the Central African State also regulates the free movement of investors, guarantees the protection of their property and families, and upholds their right to freely transfer income from investments abroad. This regulatory role prevents abuses, strengthens international partners’ confidence, and consolidates economic stability. Furthermore, by exercising its sovereignty, the State seeks to balance openness to foreign capital with decision-making autonomy. This delicate equilibrium combines investment attractiveness with protection. These objectives aim to transform foreign capital into drivers of inclusive growth. Finally, this approach enhances the country’s image, strengthens regional integration, and promotes responsible economic governance in pursuit of harmonious and sustainable development.
Keywords: Centrafrique; Economic sovereignty; Encadrement; Equal treatment; Equité; Etat; Fairness; Foreign investments; Gouvernance économique; Governance; Investissements étrangers; Protection; Regulation; Régulation; Souveraineté économique; State; Transparence; Transparency; Égalité de traitement

La hiérarchie des sources textuelles de la fiscalité minière dans les Etats francophones d’Afrique subsaharienne : le cas du Cameroun - Onana Mbida, Rodrigue Davy (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2026)
La mondialisation des échanges économiques implique des mutations profondes sur la hiérarchie des sources de la fiscalité dans l’ordre juridique interne des États. Le cas spécifique de la hiérarchie des sources de la fiscalité minière dans les États francophones d’Afrique subsaharienne constitue un exemple emblématique. Pour le démontrer, le présent article essaie d’identifier les éléments qui caractérisent la hiérarchie des sources de la fiscalité minière au Cameroun. Il ressort de cette analyse deux constats. D’un côté, la pluralité des sources légales de la fiscalité minière se précise dans un contexte de recul du monisme législatif. D’un autre côté, la prééminence dommageable des sources contractuelles au détriment des sources légales dans la taxation des activités minières s’impose aux États. Il est donc impératif pour les États d’Afrique subsaharienne comme le Cameroun de bien structurer leurs régimes fiscaux miniers afin de maximiser le prélèvement des recettes qui en découlent. The globalization of economic exchanges entails profound transformations in the hierarchy of tax law sources within the domestic legal systems of States. The specific case of the hierarchy of sources of mining taxation in French-speaking sub-Saharan African countries serves as a representative example. To demonstrate this, the present article seeks to identify the elements that characterize the hierarchy of mining taxation sources in Cameroon. The analysis reveals two main findings. On the one hand, the plurality of legal sources of mining taxation is becoming more evident in a context marked by the decline of legislative monism. On the other hand, the harmful predominance of contractual sources over legal sources in the taxation of mining activities is increasingly imposed on States. It is therefore imperative for sub-Saharan African countries such as Cameroon to properly structure their mining tax regimes in order to maximize the revenue derived from them.
Keywords: Cameroun; Contractual sources; Fiscalité minière; Hiérarchie juridique; Legal hierarchy; Legal sources; Mining taxation; Sources contractuelles; Sources légales

L’efficacité du droit OHADA dans un contexte de convergence, concurrence et harmonisation des systèmes juridiques - Sangare, Salif (Université de Montréal, 2026)
Cette étude entend contribuer au développement économique des États d’Afrique subsaharienne francophone, notamment ceux membres de l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA). En effet, les États qui constituent l’espace communautaire avaient déjà chacun dans leur sein des dispositions chargées de régir les activités économiques. Cependant, avec le temps, la disparité des normes régissant ces activités est apparue comme un frein à l’émergence économique de ces États. C’est dans ce cadre qu’ils ont décidé, lors de la signature du 17 octobre 1993 instituant l’OHADA, de mettre en place un droit commun des affaires en mesure de faciliter leur intégration juridique en promouvant le développement économique. Ce droit se veut « harmonisé, moderne et simple ». Si l’organisation a, à ce jour, adopté onze Actes uniformes couvrant plusieurs pans du droit des affaires en vue de réaliser la croissance économique prévue dans le Traité, il est important de souligner que le droit issu de l’OHADA souffre d’une certaine lourdeur liée à son enracinement non africain. Aussi, l’harmonisation du départ considérée comme le fer de lance de l’Organisation s’est matérialisée sur le terrain par une uniformisation du droit des États membres dans une société traversée par le multiculturalisme. Cette situation peut être de nature à contraindre les mœurs par le droit. On peut également ajouter à cela, le fait que le droit issu de l’OHADA est marqué par le sceau du mimétisme juridique en ce qu’il ne prenne pas en compte le secteur informel qui occupe une place très importante dans les relations d’affaires. Enfin, puisque l’enchâssement de la loi dans l’identité culturelle est l’une des conditions déterminantes de son efficacité, les précurseurs du droit OHADA auraient tout à gagner en faisant ressortir le droit OHADA des valeurs des sociétés africaines, sinon, le développement économique tant recherché de l’Afrique n’aura pas lieu. This study aims to contribute to the economic development of French-speaking sub-Saharan African countries, particularly those that are members of the Organization for the Harmonization of Business Law in Africa (OHADA). Indeed, the states that make up the community already had provisions in place to govern economic activities. However, over time, the disparity in the standards governing these activities has emerged as an obstacle to the economic emergence of these states. It was in this context that, when signing the agreement establishing OHADA on October 17, 1993, they decided to put in place a common business law capable of facilitating their legal integration by promoting economic development. This law aims to be “harmonized, modern, and simple.” While the organization has, to date, adopted eleven Uniform Acts covering several areas of business law with a view to achieving the economic growth envisaged in the Treaty, it is important to note that OHADA law suffers from a certain cumbersomeness due to its non- African roots. Thus, the harmonization that was initially considered to be the Organization's spearhead has materialized in practice as a standardization of the laws of member states in a society marked by multiculturalism. This situation may be such as to constrain customs through the law. To this can be added the fact that OHADA law is marked by legal mimicry in that it does not take into account the informal sector, which plays a very important role in business relations. Finally, since the embedding of law in cultural identity is one of the determining conditions for its effectiveness, the precursors of OHADA law would have everything to gain by highlighting the values of African societies in OHADA law; otherwise, the much sought-after economic development of Africa will not take place.
Keywords: Acte uniforme; African societies; Cultural diversity; Diversité culturelle; Droit OHADA; Développement économique; Economic development; Efficacité; Efficiency; Harmonisation; Harmonization; Intégration juridique; Legal integration; OHADA law; Sociétés africaines; Standardization; Uniform Act; Uniformisation

Les droits des personnes en matière de traitement des données sur les réseaux sociaux au Mali - Sangaré, Sékou; Diall, Yida Seydou (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2026)
Cet article analyse les droits des personnes en matière des traitements des données sur les réseaux sociaux au Mali. Soucieux d’assurer la protection de leurs données, le législateur malien a mis en place un texte portant protection des données à caractère personnelle. En plus de ce texte, une autorité a été créée en vue d’assurer la coordination et le contrôle des traitements des données personnelles. Au-delà de l’existe de la loi portant protection des données personnelles et de l’existence d’une autorité de protection, il faut relever les violations des droits des personnes en matière des traitements des données personnelles sur les réseaux sociaux à savoir, le droit d’accès à la rectification, le droit de s’informer et le droit de s’opposer. Cependant, il existe des solutions pour une effectivité des droits des utilisateurs sur les réseaux. Aux termes de celles-ci, il y a les sensibilisations, l’extension du champ d’application de la loi portant protection des données personnelles, Adoption des mesures efficaces pour un renforcement du système de sécurité, une affirmation de l’agence de la protection des données. Notre étude est basée sur la méthode documentaire et celle méthode empirique. Les deux approches combinées nous ont permis de mener une réflexion sur les droits des personnes en matière des traitements des données sur les réseaux sociaux au Mali. This article analyzes the rights of individuals in terms of data processing on social networks in Mali. Anxious to ensure the protection of their data, the Malian legislator has put in place a text on the protection of personal data. In addition to this text, an authority has been created to ensure the coordination and control of the processing of personal data. Beyond the existence of the law on the protection of personal data and the existence of a protection authority, it is necessary to note the violations of the rights of individuals in the processing of personal data on social networks, namely, the right of access to rectification, the right to be informed and the right to object. However, there are solutions for effective user rights on the networks. Under these, there are awareness-raising, the extension of the scope of the law on the protection of personal data, Adoption of effective measures to strengthen the security system, an affirmation by the agency of the Data protection. Our study is based on the documentary method and the empirical method. The two combined approaches allowed us to reflect on the rights of individuals in terms of data processing on social networks in Mali.
Keywords: Data processing; Droits des personnes; Mali; People's rights; Réseaux sociaux; Social networks; Traitement des données

La corruption et le pluralisme normatif en Afrique : vers une relecture systémique de la normativité juridique, morale et sociale - Tirvaudey, Robert (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Cette étude analyse les tensions entre droit, morale et société à travers le prisme du pluralisme normatif et de la corruption en contexte africain. Elle montre que la normativité juridique ne peut être comprise indépendamment des logiques sociales et morales qui structurent les comportements effectifs. La corruption y est appréhendée non comme une simple déviance individuelle, mais comme un phénomène systémique rationalisé, souvent intégré aux modes informels de régulation sociale et institutionnelle. L’analyse met en évidence la coexistence de plusieurs ordres normatifs (étatique, coutumier, social), dont les interactions produisent des conflits de légitimité et une relativisation des catégories classiques de faute et de responsabilité. L’étude souligne également les limites des approches répressives de la lutte contre la corruption et plaide pour une refondation de la normativité juridique fondée sur la contextualisation du droit, la reconnaissance d’une éthique publique endogène et la transformation des institutions. Elle conclut à la nécessité de penser un modèle africain de justice articulant pluralisme normatif et efficacité institutionnelle. This study examines the tensions between law, morality, and society through the lens of normative pluralism and corruption in African contexts. It argues that legal normativity cannot be understood independently from the social and moral logics that shape actual behavior. Corruption is not treated as a mere individual deviation but as a systemic and rationalized phenomenon, often embedded in informal mechanisms of social and institutional regulation. The analysis highlights the coexistence of multiple normative orders (state law, customary norms, and social norms), whose interactions generate conflicts of legitimacy and a relativization of traditional categories of fault and responsibility. The study also underlines the limitations of purely repressive anti-corruption approaches and advocates for a reconfiguration of legal normativity based on contextualized law, the recognition of an endogenous public ethics, and institutional transformation. It ultimately calls for the emergence of an African model of justice that articulates normative pluralism with institutional effectiveness.
Keywords: Corruption; Droit africain; Ethique publique; Institutions; Légitimité; Pluralisme normatif; Responsabilité; Régulation informelle

Le dol dans le cautionnement - Traoré, Amadou Tidiani (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2026)
Le cautionnement est une sûreté personnelle. II suppose l'existence d'une obligation entre un créancier et un débiteur principal. Une personne appelée caution s'engage envers le créancier à remplir l'obligation dans le cas où le débiteur principal serait incapable de se libérer à l'échéance. La caution a plusieurs définitions telles que l'engagement pris par un tiers pour garantir le paiement d'un crédit immobilier en cas de défaillance de l'emprunteur, ou le paiement en lieu et place du locataire en titre. La caution est la personne qui s'engage à garantir l'exécution d'une obligation prise par une personne (le débiteur) envers une troisième (le créancier), en cas de défaillance du débiteur. Au sens large : Le terme de caution désigne le contrat de cautionnement. Le cautionnement ne nécessite pour sa validité aucun accord préalable entre caution et débiteur. Peut se rendre caution sans ordre de celui pour lequel on s'oblige, et même à son insu. En pratique cependant le contrat de cautionnement est toujours précédé d'un tel accord, qui constitue un contrat à part entière. Or dès lors qu'on admet que la relation entre la caution et le débiteur principal revêtent une telle nature contractuelle ; l'existence d'un engagement vrai et le dol ou la simulation émanant du débiteur principal, de la caution soit du créancier méritent d'être évoqués. Le cautionnement peut être annulé sur le fondement du dol, c'est d'ailleurs l'argument le plus souvent invoqué par les cautions qui vont reprocher au créancier son manque de loyauté à la formation du contrat. Le dol n'est recevable que quand il émane du cocontractant. Pour la caution, le dol du créancier sera donc seul admissible. Le dol du débiteur n'est en principe pas pris en compte, bien qu'on puisse déceler dans ce domaine les prémisses d'une évolution. Le motif le plus fréquent d'action en nullité pour dol de la part des de la situation irrémédiablement compromise du débiteur principal au moment de l'engagement de garant. A guarantee is a personal security. It presupposes the existence of an obligation between a creditor and a principal debtor. A person called a guarantor undertakes to the creditor to fulfill the obligation if the principal debtor is unable to pay when due. A guarantee has several definitions, such as a commitment made by a third party to guarantee the payment of a mortgage loan in the event of the borrower's default, or payment in place of the tenant. Strictly speaking, a guarantor is the person who undertakes to guarantee the performance of an obligation undertaken by one person (the debtor) towards a third party (the creditor), in the event of the debtor's default. Broadly speaking, the term "guarantee" refers to the guarantee agreement itself. A guarantee does not require any prior agreement between the guarantor and the debtor for its validity. A guarantor can act as guarantor without the order of the person for whom they are obligating, and even without their knowledge. In practice, however, the guarantee agreement is always preceded by such an agreement, which constitutes a separate contract. However, once we accept that the relationship between the guarantor and the principal debtor is contractual in nature, the existence of a genuine commitment and any fraud or misrepresentation on the part of the principal debtor, the guarantor, or the creditor warrant consideration. A guarantee can be annulled on the grounds of fraud; indeed, this is the argument most often invoked by guarantors who accuse the creditor of a lack of good faith in the formation of the contract. Fraud is only admissible when it originates from the other party to the contract. For the guarantor, therefore, only fraud by the creditor is admissible. Fraud by the debtor is generally not taken into account, although the beginnings of a shift in this area can be discerned. The most frequent reason for an action to annul the guarantee based on fraud stems from the principal debtor's irremediably compromised financial situation at the time the guarantee was given.
Keywords: Cautionnement; Contract; Contrat; Creditor; Créancier; Debtor; Dol; Droit des sûretés; Débiteur; Fraud; Suretyship

Participation contrainte des tiers dans les voies d’exécution OHADA : analyse épistémologique d’une mutation du droit des obligations - Tshilumba Katambwa, Jacques; Lelo-Di-Makungu, Ursil; Dhedya Lonu, Marie-Bernard (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Le droit OHADA des voies d’exécution poursuit un objectif fondamental : assurer l’effectivité, l’efficacité et la rapidité du recouvrement des créances afin de consolider la sécurité juridique au sein de l’espace économique africain. À cet effet, l’Acte uniforme relatif à l’organisation des procédures simplifiées de recouvrement et des voies d’exécution attribue aux tiers un rôle essentiel dans la mise en œuvre des mesures d’exécution forcée, bien que ces derniers demeurent, en principe, extérieurs à la relation d’obligation initiale entre le créancier et le débiteur. La présente étude vise à examiner la participation forcée des tiers dans les voies d’exécution OHADA et à en évaluer la portée à la lumière de la théorie générale des obligations. Il ressort de cette analyse que cette participation, instituée par le législateur communautaire, a principalement pour but de garantir l’efficacité et la rapidité du recouvrement des créances, tout en mettant en évidence une évolution du rôle traditionnel du tiers dans la dynamique des obligations. Ainsi, l’intervention des tiers dans l’exécution forcée OHADA dépasse la simple dimension procédurale et reflète une transformation progressive du paradigme classique du droit des obligations, marquée par une extension fonctionnelle des acteurs participant à la réalisation des créances. The OHADA legal framework governing enforcement proceedings pursues a fundamental objective: to ensure the effectiveness, efficiency, and promptness of debt recovery in order to strengthen legal certainty within the African business environment. In this context, the Uniform Act on Simplified Debt Recovery Procedures and Measures of Execution assigns a central role to third parties in the implementation of enforcement measures, even though these actors remain, in principle, external to the original obligation binding the creditor and the debtor. This study examines the compelled participation of third parties in OHADA enforcement proceedings and assesses its implications from the perspective of the general theory of obligations. The analysis demonstrates that such participation, established by the OHADA legislator, is primarily intended to enhance the effectiveness and speed of debt recovery mechanisms, while simultaneously revealing a transformation in the traditional role of third parties within the dynamics of legal obligations. Accordingly, the involvement of third parties in OHADA enforcement procedures cannot be reduced to a mere procedural technique aimed at facilitating debt recovery. Rather, it reflects a gradual transformation of the classical paradigm of the law of obligations, characterized by a functional expansion of the actors involved in the enforcement of creditors’ rights.
Keywords: Compelled third party participation; Créances (recouvrement); Debt recovery; Droit OHADA; Droit des obligations (mutation); Enforcement proceedings; Law of obligations (transformation); OHADA Law; Participation contrainte des tiers; Privity of contract; Relativité des obligations; Third-party garnishee; Tiers saisi; Voies d’exécution

Rationalité juridictionnelle du contrôle de la saisie immobilière en droit OHADA : analyse de l’arrêt RMUA 041/040 de la Cour d’appel de la Tshopo - Tshilumba Katambwa, Jacques; Lelo-Di-Makungu, Ursil; Dhedya Lonu, Marie-Bernard (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
La saisie immobilière représente l’une des procédures d’exécution les plus structurantes du droit OHADA des voies d’exécution, en raison de la gravité de l’atteinte qu’elle porte au patrimoine du débiteur. Sa mise en œuvre soulève ainsi une problématique essentielle, à savoir la conciliation entre l’efficacité du recouvrement des créances et la protection juridictionnelle des droits du débiteur. Le présent article propose une analyse doctrinale de l’arrêt RMUA 041/040 rendu par la Cour d’appel de la Tshopo, portant sur la contestation d’un commandement aux fins de saisie immobilière. L’étude examine la manière dont la juridiction d’appel a exercé son contrôle sur la recevabilité des contestations ainsi que sur la régularité substantielle de la procédure d’exécution immobilière. Elle met en lumière le fait que la Cour d’appel ne s’est pas limitée à un contrôle formel des délais procéduraux, mais a procédé à une relecture du contentieux afin de rétablir la cohérence normative du dispositif procédural régissant la saisie immobilière. L’arrêt commenté illustre ainsi le rôle régulateur du juge dans le contentieux de l’exécution et contribue à affirmer une rationalité juridictionnelle du droit OHADA des voies d’exécution. Real estate seizure constitutes one of the most significant enforcement procedures within the OHADA legal framework governing enforcement measures, due to the severe impact it has on the debtor’s patrimonial rights. Its implementation therefore raises a fundamental issue: the reconciliation between the effectiveness of debt recovery and the judicial protection of the debtor’s rights. This article provides a doctrinal analysis of judgment RMUA 041/040 delivered by the Court of Appeal of Tshopo concerning the challenge of a command initiating real estate seizure proceedings. The study examines the manner in which the appellate court exercised its control over both the admissibility of procedural challenges and the substantive legality of the real estate enforcement procedure. The analysis highlights that the Court of Appeal did not confine its review to a merely formal assessment of procedural deadlines, but rather undertook a broader reconsideration of the litigation in order to restore the normative coherence of the procedural framework governing real estate seizure. The judgment thus illustrates the regulatory role played by the judiciary in enforcement litigation and contributes to affirming a form of jurisdictional rationality in OHADA enforcement law.
Keywords: Contrôle juridictionnel; Debt recovery; Droit OHADA; Enforceable title; Judicial review; Jurisdictional rationality; OHADA Law; Rationalité juridictionnelle; Real estate seizure; Recouvrement de créances; Saisie immobilière; Titre exécutoire

Réquisition de la force publique en droit OHADA. Entre automaticité normative de l’article 29 de l’AUPSRVE et régulation juridictionnelle interne : analyse critique des pratiques judiciaires des juridictions de la ville de Kisangani - Tshilumba Katambwa, Jacques; Lelo-Di-Makungu, Ursil; Dhedya Lonu, Marie-Bernard (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
L’exécution des décisions de justice représente l’une des conditions essentielles à l’effectivité de l’État de droit. Dans l’espace juridique de l’OHADA, cette exigence est affirmée par l’Acte uniforme relatif à l’organisation des procédures simplifiées de recouvrement et des voies d’exécution (AUPSRVE), dont l’article 29 dispose que l’État doit apporter son concours à l’exécution des décisions de justice et que la formule exécutoire équivaut à une réquisition directe de la force publique. Cette disposition instaure ainsi un mécanisme d’automaticité du concours de la puissance publique, destiné à assurer l’effectivité des titres exécutoires. Cependant, l’examen des pratiques juridictionnelles dans certaines juridictions nationales met en lumière l’existence de médiations institutionnelles susceptibles de limiter cette automaticité. C’est notamment le cas dans les juridictions de Kisangani, où la réquisition de la force publique est souvent précédée de l’intervention du ministère public. Le présent article examine les fondements juridiques et la portée normative de l’article 29 de l’AUPSRVE, puis analyse la compatibilité de ces pratiques juridictionnelles avec la logique procédurale du droit uniforme. Elle met en relief les tensions entre l’automaticité normative instaurée par le droit OHADA et les traditions procédurales nationales, tout en soulignant la nécessité d’adapter les pratiques judiciaires afin d’assurer l’effectivité du droit communautaire des voies d’exécution. The enforcement of judicial decisions constitutes a fundamental requirement for the effectiveness of the rule of law and the credibility of any judicial system. Within the OHADA legal framework, this requirement is expressly addressed by the Uniform Act on the Organization of Simplified Recovery Procedures and Measures of Execution (AUPSRVE). Article 29 of this instrument provides that the State is obliged to assist in the enforcement of judicial decisions and that the enforceable formula itself constitutes a direct requisition of public force. Through this provision, the OHADA legislator establishes a mechanism of automatic public assistance aimed at guaranteeing the effectiveness of enforceable titles and strengthening legal certainty within the OHADA economic area. However, an examination of judicial practices in certain national jurisdictions reveals the persistence of institutional mediation mechanisms that tend to limit this automaticity. This is particularly evident in the courts of Kisangani in the Democratic Republic of Congo, where the requisition of public force is frequently preceded by the intervention of the public prosecutor. This article analyses the legal foundations and normative scope of Article 29 of the AUPSRVE and critically examines the compatibility of such judicial practices with the procedural logic of OHADA uniform law. It argues that the effectiveness of the OHADA enforcement regime depends largely on the alignment of national judicial practices with the principle of automatic enforcement established by community law.
Keywords: Article 29 AUPSRVE; Automaticité du concours de l’État; Democratic Republic of Congo; Droit OHADA; Effectiveness of enforcement; Effectivité des voies d’exécution; Enforcement of judicial decisions; Exécution des décisions de justice; Judicial practices; Legal harmonization; Ministère public; OHADA law; Pratiques juridictionnelles; Procédures simplifiées; Public force requisition; Réquisition de la force publique; Voies d’exécution

La notion de recommandation numérique : essai de conceptualisation - Conte, Charlotte Le (Université de Reims Champagne-Ardenne, 2026)
Résultats de recherche, fils d’actualités, avis en ligne, communications d’influenceurs, publicités en ligne … Tout autant de pratiques incitatives permettant à l’internaute de se repérer au sein d’une offre pléthorique de contenus en ligne et pouvant a priori correspondre à l’expression de « recommandation numérique ». La notion de recommandation numérique n’a pourtant fait l’objet d’aucune conceptualisation alors même qu’il existe un régime juridique y afférent. Dès lors, la mise au jour de cette notion apparaît nécessaire afin d’identifier puis de qualifier ce qui déclenchera l’application de règles particulières.L’identification de la notion de recommandation numérique permet d’abord de la situer aux côtés de deux notions avec lesquelles elle entretient des liens de parenté parfois contradictoires : l’information et la publicité.L’étude propose dès lors deux séries de critères de qualification aptes à saisir la notion de recommandation numérique qui en impacte le périmètre. D’un point de vue matériel, la recommandation numérique possède une nature formelle : il s’agit d’un ordonnancement suggestif de contenus et non d’un contenu incitatif. Cette nature est corroborée par l’existence d’un régime juridique lui aussi formel car fondé sur la transparence, tandis que les contenus incitatifs sont soumis à des règles de fond. D’un point de vue fonctionnel, il s’agit d’une intermédiation informationnelle plus large qu'imaginée notamment parce qu'elle peut être de nature personnalisée ou non. Elle demeure néanmoins fondée sur un traitement algorithmique de données à caractère personnel ou non personnel et donc, soumise au droit des données. Search results, news feeds, online reviews, influencer communications, online advertising ... These are all incentive practices that enable internet users to find their way through a plethora of online content and could, in principle, be described as “digital recommendations”. However, the notion of digital recommendation has not been conceptualized, even though there is a legal framework governing it. It is therefore necessary to clarify this concept in order to identify and define what will trigger the application of specific rules.Identifying the notion of digital recommendation allows us to situate it alongside two concepts with which it has sometimes contradictory links: information and advertising.The study therefore proposes two sets of qualification criteria that capture the concept of digital recommendation and its scope. From a material point of view, digital recommendation is formal in nature: it is a suggestive ordering of content rather than incentive-based content. This nature is corroborated by the existence of a legal regime that is also formal, as it is based on transparency, whereas incentive-based content is subject to substantive rules. From a functional point of view, it is a broader form of information intermediation than imagined, particularly because it can be personalized or not. Nevertheless, it remains based on the algorithmic processing of personal or non-personal data and is therefore subject to data law.
Keywords: Algorithmes; Données; Droit de la consommation; Information; Intermédiation; Internet (droit); Publicité; Recommandation; Systèmes de recommandation (informatique)

L'articulation entre les actes uniformes de l'OHADA et les droits internes des États - Kpoghomou, Vahe (Village de la Justice, 2026)
L’articulation entre les actes uniformes de l’OHADA et les droits internes des États : une application directe qui n’exclut pas l’intervention du droit national.

Optimisation des services généraux de la Banque Centrale du Congo : Apport du lean management (Étude menée en 2023) - Nzapakembi Kwando, Roger; Nzembula Nyota, Ruth (International Journal of Innovation and Scientific Research, 2026)
La Banque Centrale du Congo, pilier de la stabilité économique et financière du pays, fait face à des enjeux spécifiques liés à la gestion des ressources, à l’efficacité opérationnelle et à la lutte contre la volatilité économique. Elle est confrontée à des défis croissants, notamment en matière de réactivité et d’adaptation face à des crises financières, à des fluctuations des taux de change ou encore à des exigences accrues en termes de transparence et de conformité règlementaire. Elle s’appuie sur des services internes pour assurer le bon déroulement de ses missions. Parmi eux, les Services Généraux. Nous avons constaté que, dans le quotidien de ces services, les procédures administratives sont souvent longues et complexes, entrainant des pertes de temps, des gaspillages et, une utilisation sous-optimale des moyens disponibles. Cette situation compromet la réactivité et l’efficacité de la banque dans un environnement où chaque minute compte, que ce soit pour répondre aux enjeux financiers ou pour coordonner des missions stratégiques. L’adaptation du Lean Management (Value Stream Mapping, 5S, Kaizen, etc) qui consiste à éliminer les gaspillages et ne conserver que les étapes qui apportent une réelle valeur ajoutée. Une gestion au plus juste s’est avérée particulièrement pertinente. The Central Bank of Congo, a pillar of the country’s economic and financial stability, faces specific challenges related to resource management, operational efficiency, and the fight against economic volatility. It faces growing challenges, particularly in terms of responsiveness and adaptation to financial crises, exchange rate fluctuations, and increased transparency and regulatory compliance requirements. It relies on internal departments to ensure the smooth running of its missions, including general services. We noted that, in the daily operations of these departments, administrative procedures are often lengthy and complex, leading to wasted time and suboptimal use of available resources. This situation compromises the bank’s responsiveness and efficiency in an environment where every minute counts, whether in responding to financial challenges or coordinating strategic missions. The adaptation of Lean Management (Value Stream Mapping, 5S, Kaizen, etc.), which involves eliminating waste and retaining only the steps that provide real added value, has proven particularly relevant.
Keywords: 5S; Banque Centrale; Central Bank; Kaizen; Lean Management; Optimisation; Optimization

La construction inachevée du private enforcement en Afrique de l’Ouest : inadaptation du droit commun et exigence d’une harmonisation régionale - Adai, Yao B. Vincent de Paul (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
En Afrique de l’Ouest, le droit des pratiques anticoncurrentielles s’est principalement structuré autour de la répression publique des comportements restrictifs de concurrence, assurée par les autorités nationales et par les autorités régionales de la CEDEAO et de l’UEMOA. En revanche, la réparation des préjudices subis par les victimes demeure quasi inexistante et juridiquement inachevée, soulevant la question de l’effectivité du droit des pratiques anticoncurrentielles en l’absence d’un cadre régional harmonisé de private enforcement. À partir d’une analyse normative et comparative, l’article confronte les cadres ouest-africains à l’expérience européenne, notamment celle issue de la directive 2014/104/UE sur les actions en dommages et intérêts. Il souligne les limites du recours au droit commun de la responsabilité civile pour assurer l’accès aux preuves et à la réparation effective des préjudices anticoncurrentiels. L’étude plaide pour une harmonisation régionale des actions en réparation afin de renforcer l’effectivité du droit et l’accès à la justice des victimes, consolidant ainsi la cohérence du marché régional. In West Africa, antitrust law is largely built on public enforcement of restrictive business practices, managed by regional and national authorities within ECOWAS and UEMOA. Compensation for victims, however, remains minimal and legally fragmented, raising questions about the law’s overall effectiveness without a harmonized framework for private enforcement. This article adopts a normative and comparative approach, examining West African frameworks alongside the European experience, particularly Directive 2014/104/EU on damages actions. It demonstrates that reliance on general civil liability fails to secure access to evidence or ensure effective redress for anticompetitive harm. The study argues that regional harmonization of private enforcement is essential to strengthen legal effectiveness, improve victims’ access to justice, and enhance the coherence and credibility of the West African market.
Keywords: Afrique de l'Ouest; Antitrust; CEDEAO; Civil Liability; Competition law; Droit antitrust; Droit de la concurrence; Droit des pratiques anticoncurrentielles; Droit à réparation; ECOWAS; Effectiveness of Law; Effectivité du droit; European Experience; Expérience européenne; Harmonisation régionale; Law of Anticompetitive Practices; Private Enforcement; Public Enforcement; Public enforcement; Regional Harmonization; Responsabilité civile; Right to Compensation; UEMOA; West Africa

La mobilisation des ressources fiscales dans le district de Bamako : entre insuffisances du cadre juridique et difficultés pratiques - Ballo, Mamadou (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2026)
La faible mobilisation des ressources financières en générale et, des recettes fiscales en particulier, constitue un obstacle majeur à la mise en œuvre de la politique de décentralisation au Mali. En effet, après plus trente ans de pratique, le processus de décentralisation territoriale au Mali connait toujours des difficultés de fonctionnement qui traduisent une certaine ineffectivité due à l’insuffisance des ressources financières. Les ressources fiscales en constituent une part importante. La présente réflexion se propose d’analyser les difficultés relatives à la mobilisation effective des ressources fiscales en milieu urbain, en l’occurrence le District de Bamako. Elle emprunte fondamentalement la méthode juridique notamment sous l’angle des finances locales centrées sur l’analyse des textes juridiques et des ressources doctrinales. Toutefois, il est fait parfois recours à la méthode empirique (sociologique) afin de mieux appréhender la perception des contribuables à l’égard de la législation fiscale. La première partie analyse les insuffisances du cadre juridique fiscal dont la complexité et l’incohérence contrastent avec le faible niveau d’alphabétisation des populations locales et leur manque de culture administrative. La deuxième partie, analyse les liens entre la défaillance des documents administratifs et le développement des pratiques illégales et l’incivisme fiscal. Au demeurant, la faible mobilisation des ressources fiscales constitue un défi majeur à la réussite du processus de la décentralisation. Elle n’en constitue pas le seul. La crise multidimensionnelle à laquelle le Mali est confrontée parait rédhibitoire du fait du contraste entre sécurité, défense nationale et décentralisation territoriale. Le recours actuel aux délégations spéciales, en lieux et places des Conseils élus, ainsi que la suppression des Communes urbaines et les Cercles comme collectivités, traduisent ce malaise conjoncturel sous la transition politique malienne.

Traitement des données à caractère personnel et protection de la vie privée au regard de la loi du 23 décembre 2024 relative à la protection des données à caractère personnel au Cameroun - Dié Kouénéyé, Hubert (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Le développement fulgurant du numérique a entraîné partout dans le monde la collecte, le stockage et manipulation d’importantes données à caractère personnel. C’est la raison pour laquelle dans de nombreux pays, des lois ont été adoptées pour réguler le contenu des plateformes numériques, lutter contre la contrefaçon, garantir la liberté d’expression et surtout protéger la vie privée. Suivant le mouvement, le législateur camerounais, après de nombreuses années d’hésitation, a finalement adopté le 23 décembre 2024 une loi relative à la protection des données à caractère personnel. Même si l’objectif affirmé du nouveau texte de loi est de garantir les droits et libertés fondamentaux des personnes en matière de traitement de leurs données à caractère personnel, il est question dans la présente étude d’interroger l’efficacité des garanties mises en place pour maintenir une limite raisonnable entre la collecte puis le traitement des données à caractère personnel et le respect de la vie privée des citoyens. Il ressort de l’analyse du texte que le dispositif de traitement des données offre une protection acceptable de la vie privée de la personne concernée par l’opération. Toutefois, en l’état actuel, celle-ci reste encore fragile en raison des insuffisances du texte ou de l’inexistence d’une Autorité nationale de protection des données. C’est la raison pour laquelle des solutions pouvant permettre d’optimiser la protection sont également proposées. The rapid development of digital technology has led to the collection, storage and manipulation of significant personal data worldwide. This is why in many countries, laws have been adopted to regulate the content of digital platforms, combat counterfeiting, guarantee freedom of expression, and, above all, protect privacy. Following this trend, the Cameroonian Legislator, after many years of hesitation, has finally adopted a law on the protection of personal data on December 23, 2024. Even though the stated objective of the new Law is to guarantee the fundamental rights and freedoms of individuals regarding the processing of their personal data, this study examines the effectiveness of the safeguards put in place to maintain a reasonable boundary between the collection and processing of personal data and respect of the citizens’ privacy. Analysis of the text reaveals that the data processing system offers acceptable protection of the privacy of the individual concerned. However, as it stands, this protection remains fragile due to the shortcomings in the text and the absence of a national data protection Authority. Therefore, solutions that could optimise this protection are also proposed.
Keywords: Data processing; Données à caractère personnel; Droits et libertés fondamentaux; Fundamental rights and freedom; Personal data; Protection de la vie privée; Protection of privacy; Traitement des données

La protection du consentement du consommateur lors d’une vente en exposition dans l’espace CEMAC - Djivira, Dina Mirielle (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Les ventes réalisées dans le cadre des foires et salons s’inscrivent dans un environnement promotionnel spécifique, caractérisé par une forte intensité commerciale et une mise en valeur attractive des produits. Ce contexte particulier, marqué par la multiplicité des offres, le dynamisme des techniques de vente et les contraintes propres à ces événements, est de nature à influencer le consentement du consommateur. Afin de prévenir ces risques, le législateur communautaire encadre strictement la formation du contrat en imposant aux professionnels un ensemble d’obligations destinées à assurer la transparence et la loyauté des relations contractuelles. À ce titre, les professionnels sont tenus de fournir au consommateur une information claire, précise et accessible portant notamment sur les caractéristiques essentielles des produits ou services proposés, leur prix, ainsi que leur propre identification. Ces exigences visent à permettre au consommateur de s’engager en toute connaissance de cause, en disposant des éléments nécessaires à une appréciation éclairée de l’offre. En complément de ce dispositif préventif, le droit reconnaît également au consommateur un droit de rétractation, lui offrant la faculté de revenir sur son engagement dans un délai déterminé. Ce mécanisme constitue une garantie supplémentaire de sa liberté contractuelle, en lui permettant de reconsidérer sa décision en dehors de la pression inhérente à l’environnement des foires et salons. Sales made at trade fairs and exhibitions take place within a specific promotional environment, characterized by intense commercial activity and attractive product presentation. This particular context, marked by a multitude of offers, dynamic sales techniques, and the constraints inherent to these events, can influence consumer consent. To mitigate these risks, the CEMAC regulator strictly regulates contract formation by imposing a set of obligations on businesses designed to ensure transparency and fairness in contractual relationships. As such, businesses are required to provide consumers with clear, precise, and accessible information, particularly regarding the essential characteristics of the products or services offered, their price, and their own identification. These requirements aim to enable consumers to make informed decisions, having the necessary information to make a fully informed assessment of the offer. In addition to this preventative framework, the law also grants consumers a right of withdrawal, allowing them to cancel their commitment within a specified period. This mechanism provides an additional guarantee of its contractual freedom, allowing it to reconsider its decision outside the pressure inherent in the environment of trade fairs and exhibitions.
Keywords: CEMAC; Consent (protection); Consentement (protection); Consommateur; Consumer; Exhibition sales; Vente en exposition

Le devoir de loyauté des dirigeants sociaux des sociétés commerciales en droit OHADA - Essi Bidja, Jean Marcel (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Sous l’influence, des principes du « gouvernement d’entreprise », il apparaît sans nul doute que, les dirigeants sociaux sont tenus, d’abord, par un devoir de loyauté envers les associés de la société, par un devoir de même nature, ensuite envers la société. Il s’agissait de savoir comment ce devoir général et théorique trouvait à se manifester. Le parti a été pris d’organiser les différentes manifestations du devoir de loyauté des dirigeants sociaux en droit OHADA dans ses rapports internes et externes, selon un plan thématique, aussi il peut être complémentaire de les rappeler dans un ordre plus formel. Under the influence of “corporate governance” principles, it appears clear that corporate officers are bound, first, by a duty of loyalty toward the shareholders of the company, and subsequently, by a duty of the same nature toward the company itself. The central question was how this general and theoretical duty is manifested in practice. The approach taken was to organise the various manifestations of the duty of loyalty of corporate officers under OHADA law in both internal and external relations. While these are presented according to a thematic plan, it may also be useful to recall them in a more formal order.
Keywords: Associés; Concurrence déloyale; Corporate officers; Devoir; Dirigeants sociaux; Duty; Loyalty; Loyauté; Shareholders; Unfair competition

De l'impartialité du juré d'assises - Frugier, Cindy (Université de Bordeaux, 2026)
Nos recherches se concentrent sur une définition de l’impartialité du juré, sur les garanties procédurales de celles-ci, tendant à prévenir la libre formation de leur intime conviction. La subjectivité, lorsqu’elle expose le juré au regard d’autrui, dans le prétoire oudans le cadre d’un procès médiatisé, accroît le risque d’un défaut d’impartialité subjective qui, mal maîtrisée, mettrait à mal son devoir d’impartialité. Our research focuses on defining jury impartiality and the procedural safeguards that protect it, aiming to prevent jurors from freely forming their own personal convictions. Subjectivity, when it exposes the juror to the scrutiny of others, whether in the courtroom orduring a televised trial, increases the risk of a lack of subjective impartiality which, if poorly managed, could undermine their duty of impartiality.
Keywords: Awareness; Conscience; Cours d'assises; France; Impartialité; Indépendance judiciaire; Influence; Intimate conviction; Intime conviction; Jury; Motivation; Prejudice; Procédure pénale; Préjugé; Rationalisation; Rationalization

Réflexion sur la responsabilité sociale des entreprises multinationales extractives en droit international africain des droits de l’homme - Ipala Atangana, Vanessa (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2026)
La responsabilité sociale des entreprises multinationales extractives constitue une préoccupation croissante en Afrique, au regard de ses incidences sur les droits de l’Homme, l’environnement et le développement. Dans le contexte du droit international africain des droits de l’Homme, cette responsabilité s’inscrit dans un cadre normatif encore en construction, où se croisent exigences économiques et impératifs de protection des populations. Dès lors, peut-on parler d’un régime de Responsabilité Sociale des Entreprises multinationales extractives en Droit international Africain des D-H ? A travers la méthode analytique, comparative et prospective, l’analyse met en évidence une responsabilité juridiquement ambiguë, révélant d’une part, l’émergence d’une responsabilité à vocation juridique et, d’autre part, la constance d’une responsabilité à portée limitée. The social responsibility of multinational extractive companies is a growing concern in Africa, given its impact on Human rights, the environment, and development. Within the context of African international Human rights law, this responsibility is situated within a still-evolving normative framework where economic demands intersect with the imperatives of protecting populations. Therefore, can we speak of a corporate social responsibility regime extractive multinational in African international human rights law? Through an analytical, comparative, and prospective approach, this analysis highlights a legally ambiguous responsibility, revealing, on the one hand, the emergence of a liability with a legal vocation and, on the other hand, the constancy of limited scope liability.
Keywords: African international law; CSR; Droit international africain; Droits de l’Homme; Entreprises multinationales extractives; Human rights; Legal remedies; Multinational extractive companies; RSE; Recours juridiques; Responsabilité sociale; Social responsibility

Analyse des conséquences d’exclusion du droit au travail décent des personnes vivant avec handicap en République Démocratique du Congo - Kalongo Monokela, Jonas; Lelo-Di-Makungu, Ursil; Dhedya Lonu, Marie-Bernard; Lokesa Bomboli, Paul-Ruffin; Djeze Zonga, Jupson; Lungele Mulima, Georges (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Le travail décent est celui qui tient compte de la dignité humaine et se matérialise par une rémunération non seulement juste mais aussi équitable. L’inclusion au travail décent demeure jusqu’à ce la voie principale pour le développement économique d’un Etat. Cependant, la présente étude tend à analyser les conséquences d’exclusion du droit au travail décent des personnes vivant avec handicap en République Démocratique du Congo qui se dégagent suite au non-respect de la loi nº22/003 du 3 mai 2022 qui consacre le droit au travail décent pour les personnes vivant avec handicap. Pour y arriver, la sociologie du droit est la stratégie mobilisée pour cette étude avec la technique d’enquête accompagnée par celle de l’interview libre. Ainsi, nous avons abouti aux résultats suivants : Le non-respect de la loi en matière de droit au travail décent pour les personnes vivant avec handicap engendre comme conséquences, les violations des obligations constitutionnelles et légales nationales, la responsabilité internationale de l’Etat congolais, l’aggravation de la pauvreté, le sous-développement national, la diminution des recettes publiques, la marginalisation et exclusion sociale, le chômage, la réduction des opportunités, Dépendance familiale accrue, des tensions et conflits familiaux. Decent work is one that takes into account human dignity and is manifested through remuneration that is not only fair but also equitable. Inclusion in decent work remains the main pathway to the economic development of a state. However, this study aims to analyze the consequences of excluding the right to decent work for persons with disabilities in the Democratic Republic of the Congo, which arise from the non-compliance with law no. 22/003 of May 3, 2022, which enshrines the right to decent work for persons with disabilities. To achieve this, the sociology of law is the strategy employed for this study, utilizing a survey technique accompanied by free interviews. Thus, we arrived at the results: Non-compliance with the law regarding the right to decent work for persons with disabilities leads to consequences such as violations of constitutional and national legal obligations, international responsibility of the Congolese state, worsening poverty, national underdevelopment, reduced public revenue, marginalization and social exclusion, unemployment, decreased opportunities, increased family dependency, and tensions and conflicts within families.
Keywords: Consequence; Conséquence; Decent work; Exclusion; Person with disabilities; Personne vivant avec handicap; Travail décent

Les obstacles à l’intégration sous régionale en Afrique Centrale : Une analyse des contraintes politiques et des défis sécuritaires en zone CEMAC - Maina Kampete, Lady (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
L’intégration sous-régionale constitue un objectif majeur pour les États d’Afrique centrale réunis au sein de la Communauté économique et monétaire de l’Afrique centrale (CEMAC). Malgré l’adoption de nombreux instruments juridiques et politiques visant à favoriser la libre circulation des personnes, des biens et des services, les résultats demeurent limités. Cet article analyse les contraintes politiques et sécuritaires qui entravent le processus d’intégration régionale dans la zone CEMAC. À partir d’une analyse institutionnelle et politique, il met en évidence la prééminence persistante des logiques souverainistes des États membres, la faiblesse de la gouvernance communautaire ainsi que l’impact des défis sécuritaires sur la gestion des frontières et la mobilité régionale. L’étude montre que l’attachement des États à leurs prérogatives nationales, combiné à l’insuffisance des mécanismes de sanction et à la multiplication des contrôles administratifs aux frontières, contribue à fragiliser l’effectivité du droit communautaire. Par ailleurs, les crises sécuritaires régionales et les tensions politico-sécuritaires entre États membres accentuent la fragmentation de l’espace régional et limitent les dynamiques d’intégration. Notre article conclut que le renforcement des institutions communautaires, l’harmonisation effective des normes et l’amélioration de la coopération sécuritaire apparaissent comme des conditions indispensables à la consolidation du processus d’intégration en Afrique centrale. Regional integration has long been considered a key instrument for economic development and political cooperation in Central Africa. Within this framework, the Economic and Monetary Community of Central Africa (CEMAC) was established to promote economic convergence, market integration, and the free movement of people and goods among its member states. However, despite the adoption of several legal and institutional frameworks aimed at facilitating regional integration, the outcomes remain limited. This article examines the political and security constraints that hinder regional integration within the CEMAC area. Using an institutional and political analysis, it highlights the persistence of strong sovereignist logics among member states, the weaknesses of regional governance, and the impact of security challenges on border management and regional mobility. The study shows that the strong attachment of states to national sovereignty, combined with the limited enforcement capacity of community institutions and the absence of effective sanction mechanisms, undermines the effective implementation of community law. In addition, security crises and political tensions within the region contribute to the fragmentation of the regional space and restrict the mobility of people and goods.The findings suggest that strengthening community institutions, improving the enforcement of regional regulations, and enhancing security cooperation among member states are essential conditions for achieving effective regional integration in Central Africa.
Keywords: Afrique centrale; CEMAC; Central Africa; Free Movement; Gouvernance; Governance; Intégration régionale; Libre circulation; Regional Integration; Security; Souveraineté; Sovereignty; Sécurité

Le clair-obscur du rebond du débiteur dans les procédures collectives en droit OHADA - Meva'A, Gérard Müller (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
L’Acte uniforme portant procédures collectives d’apurement du passif révisé a permis au débiteur honnête mais malchanceux de pouvoir se réinsérer dans le circuit économique et social à travers le rebond par la purge de ses dettes. Mais, ce droit au rebond en faveur du débiteur n’est pas totalement garanti au regard de la diversité des obstacles et des nécessités qui doivent être prises en compte dans le cadre d’un tel rebond. L’ambition de la présente étude est de démontrer que malgré la légitimation du droit au rebond du débiteur qui lui permet de bénéficier de l’effacement de ses dettes, le législateur OHADA a veillé à ce que les ajustements opérés ne profitent pas uniquement au débiteur. The revised uniform Act on collective procceedings has enabled honest but unfortunate debtor to reintegrate into the economic and social system through debt discharge. However, this right to debt discharge is not fully guaranteed, given the various obstacles and necessities that must be considered in such a process. The aim of this study is to demonstrate that, despite the institution of debt discharge, which allows him to benefit from the cancellation of his debts, the OHADA legislator has ensure that the adjustments made do not solely benefit the debtor.
Keywords: Collective procceedings; Debt discharge; Debtor; Droit OHADA; Débiteur; Obstacles; Procédures collectives; Purge des dettes; Rebond; Rebound

La neutralisation des sanctions prononcées par le juge pénal à travers le détournement des évacuations sanitaires - Nanga, Grace (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Pendant l’exécution de la sanction pénale prononcée par le juge, le condamné malade peut bénéficier d’une évacuation sanitaire afin de mieux de se soigner. Mais cette pratique des évacuations sanitaires est utilisée malicieusement par le pouvoir exécutif comme technique d'inexécution des peines privatives de liberté. Elle est tantôt injustifiée, tantôt justifiée. Ces évacuations peuvent être justifiées par la nécessité de sauver la vie d’un patient ou de prévenir des complications graves pour sa santé. Cette justification peut être aussi bien d’ordre personnel qu’infrastructurel. Si la pratique des évacuations sanitaires permet au pouvoir exécutif de neutraliser malicieusement les peines prononcées à l’encontre des condamnées, il faut tout de même retenir que cette pratique reste injustifiée puisqu’elle est non seulement sélective mais prolongée. During the execution of the penal sanction pronounced by the judge, the sick convict can benefit from a medical evacuation in order to better treat himself. But the practice of medical evacuation is mischievously used by the executive power as a technique for enforcing custodial sentences. It is sometimes unjustified, sometimes justified. Such evacuations may be justified by the need to save a patient's life or prevent serious health complications. This justification can be both personal and infrastructural. While the practice of medical evacuations enables the executive to maliciously neutralize the sentences handed down to convicted prisoners, it must be remembered that this practice remains unjustified, since it is not only selective but prolonged.
Keywords: Evacuation sanitaire; Medical evacuation; Neutralisation; Neutralization; Penal sanction; Sanction pénale

Fiscalité et informalité économique des petites et moyennes entreprises dans la Province de la Tshopo - Ndeli Ndeli, Hilaire; Bofoe Lokangu, Starmans; Tchombe Uyindo, Patrick; Mosema, Ambasu; Mbula Mapanza, Cadette; Milambo, Anifa Monica; Litwanga Ifndjaka, Jean-Pierre; Kalongo Monokela, Jonas (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Cette étude analyse l’interaction qui existe entre la persistance des Petites et Moyennes Entreprises (PME) dans l’informalité et la pression fiscale provinciale à Kisangani. Le constat est que malgré l’existence d’un cadre fiscal sur la formalisation des entreprises, le nombre des entreprises œuvrant dans l’économie informelle est très réduit. La recherche s’interroge sur l’efficacité des mécanismes de mobilisation des recettes provinciales. La présente recherche a fait appel à l’exégèse juridique et à la sociologie du droit comme méthode de recherche et repose sur une approche hybride, combinant une analyse documentaire pour les données secondaires et enquête pour les données primaires (terrain) auprès d’un échantillon raisonné de 40 PME, y compris les agents des administrations fiscales. Les résultats relèvent que 80% des enquêtés considèrent l’impôt comme une charge pour leurs activités et 60% des entreprises fonctionnent dans l’informalité. L’étude met en exergue un paradoxe institutionnel : la province met beaucoup plus l’accent sur la mobilisation des recettes que sur la promotion des PME, provoquant ainsi une pression fiscale et des stratégies de contournement (évitement spatial, corruption et négociation informelles). La recherche démontre que l’informalité des PME à Kisangani n’est pas une question de mauvaise foi ni de manque de civisme fiscal, mais mécanisme rationnel de survie face à un système fiscal inadapté. Elle préconise une transition d’une fiscalité de prélèvement vers une fiscalité de promotion pour éviter le cercle vicieux de dépendance budgétaire. This study analyzes the interaction between the persistence of Small and Medium Enterprises (SME) in informality and provincial tax pressure in Kisangani. The observation is that despite the existence of a tax framework for the formalization of businesses, the number of businesses operating in the informal economy is very small. The research questions the effectiveness of the mechanisms for mobilizing provincial revenue. The present research used legal exegesis and the sociology of law as a research method and is based on a hybrid approach, combining documentary analysis for secondary data and surveys for primary data (field) from a reasoned sample of 40 SMEs, including agents from tax administrations. The results show that 80% of respondents consider tax as a burden on their activities and 60% of businesses operate in informality. The study highlights an institutional paradox: the province places much more emphasis on revenue mobilization than on the promotion of SMEs, thus causing tax pressure and circumvention strategies (spatial avoidance, corruption and informal negotiation). The research demonstrates that the informality of SMEs in Kisangani is not a matter of bad faith or lack of tax compliance, but a rational survival mechanism in the face of an inadequate tax system. It advocates a transition from a levy-based tax system to a promotion-based tax system to avoid the vicious cycle of budgetary dependence.
Keywords: Corruption; Economic Informality; Fiscalité provinciale; Fraude fiscale; Informalité économique; PME; Petites et Moyennes Entreprises; Provincial Taxation; SMEs; Secteur informel; Small and Medium Enterprises; Tax fraud

La répression des atteintes à la propriété foncière au Cameroun : enjeux d’une quête redoutable - Nkoa, François Nestor Patrice (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
La protection effective et efficace de la propriété foncière par le droit pénal nécessite l’existence des normes et des règles juridiques modernes et applicables. Il est important à cet effet d’avoir une législation foncière suffisamment cohérente, un cadre juridique opérationnel et performant. S’il est vrai qu’en la matière, le législateur camerounais a mis en place un arsenal juridique adéquat, il n’en demeure pas moins vrai que l’applicabilité de ces textes en pratique reste hypothétique. De même, à l’aune des mutations du droit foncier et de nombreuses exigences en matière de protection de la propriété foncière, il incombe un renforcement des outils existants pour une répression réussie. The effective and efficient protection of land ownership through criminal law requires the existence of modern and applicable legal norms and rules. To this end, it is important to have sufficiently coherent land legislation and an operational and effective legal framework. While it is true that the Cameroonian legislature has established an adequate legal arsenal in this area, the practical applicability of these texts remains uncertain. Similarly, in light of the evolving landscape of land law and the numerous requirements for land ownership protection, it is essential to strengthen existing tools for successful enforcement.
Keywords: Achievement; Atteinte; Criminal law; Droit foncier; Droit pénal; Incrimination; Land property; Ownership; Propriété foncière; Protection; Repression; Répression

L’anachronisme du fondement juridique du contrat - Padjonre, Bernard (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
En droit civil, le contrat se définit comme étant une convention par laquelle une ou plusieurs personnes s’obligent envers une ou plusieurs autres personnes à donner, à faire ou ne pas faire quelque chose. De cette définition, il ressort très clairement que le contrat avait classiquement pour seul fondement la volonté. Or de nos jours, tenant compte de grandes mutations sur les plans économique, technologique et juridique, l’autonomie de la volonté contractuelle reposant sur la volonté, a cessé de la considérer comme l’unique fondement du contrat : d’où l’éclosion des autres fondements dits modernes pour lesquels notre présente réflexion va mettre en exergue à travers les différents courants doctrinaux. In civil law, a contract is defined as an agreement whereby one or more persons undertake to give, do, or refrain from doing something to one or more other persons. From this definition, it is very clear that contracts were traditionally based solely on the will of the parties. However, today, given the major economic, technological, and legal changes that have taken place, the autonomy of contractual will based on free will is no longer considered the sole basis of a contract. This has led to the emergence of other, so-called modern bases, which we will highlight in this discussion through the various doctrinal currents.
Keywords: Anachronism; Anachronisme; Contract; Contrat; Fondement juridique; Legal basis

L’émergence de IA génératives : impacts socio-économiques et cadre juridique - Traoré, Penda (Université de Montréal, 2026)
Le monde du numérique et des technologies ne cesse d’évoluer, porté par des innovations toujours plus avancées, à l’instar de l’intelligence artificielle générative, issue d’un long processus de développement des systèmes intelligents. Cette technologie s’est rapidement imposée comme un sujet central en raison des nombreuses opportunités et avantages qu’elle offre tant aux individus qu’aux entreprises et à l’économie dans son ensemble. Elle a profondément transformé les modes de travail et les pratiques professionnelles dans de nombreux secteurs. Cependant, cette technologie a vite montré ses limites car elle engendre de nombreux risques surtout sur le plan éthique et sur le plan de la protection des renseignements personnels. La problématique de la confiance numérique et du respect de la vie privée a soulevé d’énormes initiatives et débats afin de savoir comment limiter les risques de cette technologie et favoriser son développement. Tous ces faits ont motivé ce mémoire qui propose d’abord un état des lieux de l’intelligence artificielle générative, en mettant en lumière les risques qui lui sont associés, avant d’aborder les cadres juridiques encadrant ces technologies. En effet, tout dispositif de régulation suppose une compréhension préalable du fonctionnement et des vulnérabilités du système concerné. L’objectif principal est ainsi d’analyser les modèles d’intelligence artificielle à l’aune de leurs risques, en s’interrogeant sur leur capacité à adopter un comportement conforme aux exigences éthiques. Pour la réalisation de cette objectif une expérience on a mené une expérience sur différents modèles d’intelligence artificielle générative auxquels nous avons ingéré plusieurs prompts similaires et ensuite étudier les résultats de chaque modèle afin de déceler des réponses anormales et la présence ou non de biais dans les résultats. The world of digital technology is constantly evolving, driven by ever more advanced innovations, such as generative artificial intelligence, the result of a long process of developing intelligent systems. This technology quickly established itself as a central topic due to the numerous opportunities and benefits it offers to individuals, businesses, and the economy. It has profoundly transformed working methods and professional practices in many sectors. However, this technology quickly revealed its limitations, as it generates numerous risks, particularly from an ethical perspective and in terms of the protection of personal information. The issue of digital trust and privacy has sparked enormous initiatives and debates to determine how to limit the risks of this technology and promote its development. All these facts have motivated this thesis, which first provides an overview of generative artificial intelligence, highlighting the associated risks, before addressing the legal frameworks governing these technologies. Indeed, any regulatory mechanism presupposes a prior understanding of the functioning and vulnerabilities of the system in question. The main objective is thus to analyze artificial intelligence models considering their risks, by questioning their ability to adopt behavior consistent with ethical requirements. To achieve this objective, an experiment was conducted on different generative artificial intelligence models, to which we fed several similar prompts and then studied the results of each model to detect abnormal responses and the presence or absence of bias in the results.
Keywords: Cadre juridique; Cybersecurity; Cybersécurité; Ethics; Generative artificial intelligence; Intellectual property; Intelligence artificielle générative; Legal framework; Propriété intellectuelle; Protection des renseignements personnels; Protection of personal information; Respect de la vie privée; Respect for privacy; Éthique

Les transformations numériques et la norme juridique en droit du travail : vers l’instauration d’un milieu éthique de la relation professionnelle - Mnaouer, Mouhcine; Himmich, Mohammed Chakib (Revue Internationale Burak des Etudes Juridiques et Economiques, 2026)
À l’ère de la transformation numérique, le monde du travail connaît une mutation profonde, marquée par l’intégration croissante des technologies digitales et de l’intelligence artificielle dans les relations professionnelles. Ces innovations, porteuses d’efficacité et de modernisation, soulèvent néanmoins d’importants défis juridiques et éthiques relatifs à la protection des droits fondamentaux du salarié. Dans ce contexte, le présent article se propose d’analyser les mécanismes par lesquels la norme juridique en droit du travail marocain peut accompagner ces mutations, tout en garantissant l’instauration d’un milieu professionnel éthique, conciliant innovation technologique, équité et dignité humaine. L’objectif central de ce travail est de démontrer la nécessité d’un encadrement juridique adapté aux exigences du numérique, afin de prévenir les dérives possibles, telles que l’atteinte à la vie privée, la collecte abusive de données personnelles ou encore les discriminations algorithmiques dans les processus d’embauche et de licenciement. Ainsi, l’étude met en lumière la portée limitée des textes actuels et plaide pour une réforme cohérente intégrant des droits émergents, notamment le droit à la déconnexion, la protection des données à caractère personnel, ainsi que le principe d’égalité de traitement dans l’usage de l’intelligence artificielle. Par ailleurs, l’analyse s’articule autour de deux axes complémentaires : le premier examine les exigences de protection de la vie privée et des données personnelles à l’ère du numérique ; le second explore les défis d’équité soulevés par l’intelligence artificielle dans la gestion des relations de travail. Ce travail ambitionne, in fine, de contribuer à la réflexion sur la construction d’un droit du travail marocain moderne, équilibré et porteur d’une éthique de responsabilité numérique. In the era of digital transformation, the world of work is undergoing profound change, marked by the growing integration of digital technologies and artificial intelligence into professional relations. While these innovations foster efficiency and modernization, they also raise significant legal and ethical challenges concerning the protection of workers’ fundamental rights. In this context, this article seeks to analyze how labour law norms in Morocco can accompany these transformations while ensuring the establishment of an ethical professional environment that reconciles technological innovation, equity, and human dignity. The main objective of this study is to demonstrate the urgent need for a legal framework adapted to the requirements of the digital age, in order to prevent potential abuses such as infringements of privacy, the misuse of personal data, and algorithmic discrimination in recruitment and dismissal processes. The research highlights the limited scope of current legislation and advocates for a coherent reform integrating emerging rights, including the right to disconnect, the protection of personal data, and the principle of equal treatment in the use of artificial intelligence. The analysis is structured around two complementary axes: the first examines the requirements for protecting privacy and personal data in the digital workplace; the second explores the equity challenges raised by artificial intelligence in the management of employment relations. Ultimately, this work aims to contribute to the reflection on building a modern Moroccan labour law that is balanced, forward-looking, and grounded in a genuine ethics of digital responsibility.
Keywords: Artificial Intelligence; Data Protection; Digital Transformation; Droit du travail; Intelligence artificielle.; Labour Law; Professional Ethics; Protection des données personnelles; Transformation numérique; Éthique professionnelle

L’impact des clauses d’arbitrage entre investisseurs étrangers et Etats sur la souveraineté : une analyse de l'équilibre entre protection des investisseurs étrangers et la souveraineté - Ahouyanganga Matondo, Dan Salomon (Université de Montréal, 2026)
Ce mémoire analyse l’impact des clauses d’arbitrage entre investisseurs étrangers et États sur la souveraineté étatique, en s’intéressant à l’équilibre entre protection des investisseurs et capacité réglementaire des États. Dans un contexte de mondialisation marqué par les crises sanitaires et les tensions géopolitiques, les États cherchent à attirer les investissements étrangers tout en préservant leur souveraineté économique. Le travail met en lumière le rôle du mécanisme RDIE, permettant aux investisseurs étrangers de contester les mesures étatiques devant des tribunaux arbitraux internationaux, contournant ainsi les juridictions nationales. Bien qu’il sécurise les flux d’investissements et renforce la confiance des investisseurs, le RDIE peut créer des déséquilibres, limitant la marge de manœuvre des États dans des domaines sensibles tels que la santé publique, l’environnement ou les droits sociaux. À travers l’analyse de cas emblématiques et des traités internationaux d’investissement, le mémoire propose des pistes pour concilier la protection juridique des investisseurs et le respect de la souveraineté étatique. Il conclut que le RDIE, tout en étant un outil essentiel de sécurisation des investissements, nécessite des réformes pour garantir un équilibre durable entre intérêts privés et intérêt général. This research study will analyze the impact of arbitration clauses between foreign investors and states on state sovereignty, focusing on the balance between investor protection and the regulatory capacity of states. In a globalized context marked by health crises and geopolitical tensions, states seek to attract foreign investment while preserving their economic sovereignty. The study highlights the role of the ISDS mechanism, which allows foreign investors to challenge state measures before international arbitration tribunals, thus bypassing national courts. Although it ensures investment flows and strengthens investor confidence, the ISDS system can create imbalances, limiting states' room for maneuver in sensitive areas such as public health, the environment, and social rights. Through analysis of historical cases and international investment treaties, the thesis proposes ways to reconcile legal protection for investors with respect for state sovereignty. It concludes that while ISDS remains an essential tool for securing investments, it requires reform to ensure a sustainable balance between private interests and the public good.
Keywords: Arbitration clauses; Clauses d’arbitrage; Foreign investors; ISDS; Investisseurs étrangers; Investment treaties; RDIE; Souveraineté; Sovereignty; States; Traités d’investissement; États

L’adaptation du système d’état civil au défi contemporain de la sécurisation de l’identité des personnes au Cameroun - Edimo, François (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
L’un des fléaux qui minent la société camerounaise est l’insécurité de l’identité des personnes. Celle-ci se caractérise par l’intrusion dans la vie privée à travers l’usurpation des identités ou la fraude documentaire. Prenant la mesure du phénomène et du danger auquel il expose l’Etat, le législateur a entrepris si ce n’est de les éradiquer, au moins d’en réduire l’ampleur. A cet effet, les lois n°2024/016 du 23 décembre 2024 portant organisation du système d’enregistrement des faits d’état civil au Cameroun, n° 2024/017 du 23 décembre 2024 relative à la protection des données à caractère personnel au Cameroun et la n° 2010/012 du 12 décembre 2010 relative à la cybersécurité et à la cybercriminalité au Cameroun, ont été promulguées. De même, le BUNEC a été créé. La présente contribution ambitionne de démontrer comment ce dispositif normatif parvient à sécuriser l’identité des individus. L’analyse du contenu des différents textes donne de constater que les Pouvoirs Publics ont adopté les garanties de protection de l’intégrité des faits d’état civil et les garanties de protection des données à caractère personnel. One of the scourges undermining Cameroonian society is the insecurity of individuals’ identities. This is characterised by intrusion into private life through identity theft or document fraud. Recognising the scale of the phenomenon and the danger it exposes the State to, the legislature has undertaken, if not to stamp it out, at least to reduce its scope. To this end, Laws n°2024/016 of 23 December 2024, on the organisation of the civil registration system in Cameroun, n°2024/017 of 23 December 2024 on protection of personnal data in Cameroun and n°2010/012 of 12 December 2010 relating to cybersecurity and cybercrime in Cameroun, were issued. Similarly, the National Bureau of Civil Status was created. This contribution aims to demonstrate how this regulatory framework manages to secure the identity of individuals. Analysis of the content of the various texts shows that the public authorities have adopted guarantees to protect the integrity of civil status records and guarantees to protect personal data.
Keywords: Anonymisation; Anonymysation; Cybersecurity; Cybersécurité; Digital identity; Données à caractère personnel; Faits d’état civil; Identité numérique; Personal data; Vital event

Le pouvoir décisionnel des conseils d’administration des établissements publics de l’État au Burkina Faso - Guigma, Hamadou (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2026)
Le Conseil d’administration (CA) bénéficie d’un éventail d’attributions statutaires respectueuses de l’autonomie fonctionnelle et de la spécialité de l’établissement public avec pour finalité de pourvoir à leur fonctionnement efficace. Mais, la qualité décisionnelle des CA s’en trouve fragilisée en raison des nécessités de maintenir une cohérence institutionnelle et normative dans le champ des secteurs publics et parapublics dans un contexte d’État unitaire. Malgré des réformes successives réalisées ces dix dernières années, les Conseils d’administration peinent, à avoir non seulement une capacité d’influence sur la sélection des premiers responsables des établissements publics mais également, à bénéficier d’un dispositif cohérent de contrôle de performance. The Board of Directors (BoD) has a range of statutory powers that respect the functional autonomy and specialization of public institutions, with the aim of ensuring their effective operation. However, the quality of the BoD’s decision-making is undermined by the need to maintain institutional and regulatory consistency across the public and semi-public sectors in a unitary state context. Despite successive reforms over the past ten years, boards of directors struggle not only to influence the selection of senior managers in public institutions, but also to benefit from a coherent performance monitoring system.
Keywords: Administrateurs; Autonomie fonctionnelle; Board of Directors; Chief Executive Officer; Conseil d’administration; Contrôle de performance; Decision-making power; Deliberations; Directeur général; Directors; Décentralisation technique; Délibérations; Etablissements publics; Functional autonomy; Membres administrateurs; Performance monitoring; Pouvoir décisionnel; Principe de spécialité; Principle of specialization; Public institutions; Sociétés d’États; State-owned companies; Technical decentralization; Unitary State; board members; État unitaire

Effectivité du droit au travail décent pour les personnes avec handicap en RDC : Entre norme juridique et réalités sociales - Kalongo Monokela, Jonas; Ezepambale Gakea, Jonathan; Dhedya Lonu, Marie-Bernard; Lelo-Di-Makungu, Ursil; Kakumbi Belumba, Grison-Trésor (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Le travail décent est aspect important figurant par les droits économiques, sociaux et culturels en République Démocratique du Congo (RDC). Cependant, tout le monde peut accéder à cette prérogative sans discrimination en rapport avec la race, l’origine ou le handicap à condition de remplir les critères imposés pour le poste d’emploi. Cette étude analyse l’effectivité du droit au travail décent pour les personnes avec handicap en RDC, en confrontant les textes légaux, notamment la loi nº22/003 du 3 mai 2022 portant protection et promotion des droits de la personne avec handicap aux réalités sociales marquées par certains défis d’ordre institutionnel, social et économique. C’est dans cette optique que l’on se propose d’analyser la législation en vigueur ainsi que son application et d’identifier les principaux obstacles qui limitent l’accès au travail décent pour les personnes avec handicap en RDC. Pour y arriver, la dogmatique juridique est la stratégie mobilisée avec la technique documentaire et celle de l’interview libre. Ainsi, nous avons abouti aux résultats selon lesquels il se remarque la non-application de la loi en matière du droit au travail décent pour les personnes avec handicap en RDC, c’est ce qui justifie la persistance de la discrimination, les préjugés, difficulté d’accès à l’éducation ou la formation. Decent work is an important aspect among the economic, social, and cultural rights in the Democratic Republic of Congo (DRC). However, everyone can access this prerogative without discrimination based on race, origin, or disability, provided they meet the criteria imposed for the job position. This study analyzes the effectiveness of the right to decent work for persons with disabilities in the DRC, confronting legal texts, notably Law No. 22/003 of May 3, 2022, concerning the protection and promotion of the rights of persons with disabilities, with social realities marked by certain institutional, social, and economic challenges. It is in this perspective that we propose to analyze the existing legislation as well as its application and to identify the main obstacles that limit access to decent work for persons with disabilities in the DRC. To achieve this, legal dogmatics is the strategy employed along with documentary techniques and free interviews. Thus, we have concluded that there is a noticeable non-application of the law regarding the right to decent work for persons with disabilities in the DRC, which justifies the persistence of discrimination, prejudice, and difficulties in accessing education or training.
Keywords: Auto-exclusion; Decent work; Disability; Discrimination; Droit; Handicap; Right; Self-exclusion; Travail décent

The effectiveness of the rights and duties of parties in contracts of probationary hiring under cameroonian labour code - Mboin, Chah Yvonne (International Multilingual Journal of Science and Technology, 2026)
Contracts of probationary hiring in Cameroon is regulated by section 28 of Law no. 92/007 of 14 August 1992 on the Cameroonian labour code and ministerial Order No. 017/MTPS/SG/CJ to sets the terms of probationary period in Cameroon. The formation of contracts of probationary hiring imposes obligations both on the employer and the employee. On the part of the employer, he has rights and obligations such as; the right to manage the worker(s), the right to discipline the employee, regulatory powers of the employer, obligations to respect fundamental rights, duty to pay wages, duty to provide work, duty to respect weekly Rest. On the part of the employee, he has rights and obligations such as, the right to privacy, the right to payment, the joint trade union, and the obligation of obedience, the obligation loyalty, skills, obligation of secrecy and more. It is a duty on both parties to respect their obligations in the contract as establish by the law. However, the weaker party in contracts of the probationary hiring which is the employee continue to see his rights been constantly violated on daily bases by the employer. Most employers violate the right to payment, good working conditions and even weekly rest of employees during period of probationary hiring. This continues to persist because a lot of worker is in vulnerable positions and needs jobs. Some workers are not even aware of the rights available to them in these contracts of employments. This research work has as objective to examine how effective are the rights and obligations of parties respected in contracts of probationary hiring under the Cameroonian labour code. A doctrinal research methodology has been adopted where both primary and secondary sources of information haven been consulted. Our findings reveal that, most employees are the ones whose rights are constantly violated in contracts of probationary hiring on daily basis in Cameroon because of their vulnerability, ignorance and improper implementation of the law regulating contracts of probationary hiring. As a result we recommend that, the state should ensure the effective implementation of the labour legislation in Cameroon, there should be general sensitization of Cameroonians on their rights in contracts of probationary hiring in Cameroon.
Keywords: Droit du travail; Duties; Probationary hiring; Période probatoire; Recrutement; Rights

La preuve dans le droit des assurances dommages de la CIMA - Ngoume Ondoua, Jean Aimé (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
La preuve dans les assurances, à l’instar de tous les domaines du droit, joue un rôle déterminant dans l’issue du procès. Le domaine des assurances étant spécifique et complexe, l’on est en droit de se poser la question de savoir si le régime juridique de la preuve en assurance se distingue véritablement de celui du droit commun à l’effet de mieux protéger les parties ? L’étude fait simplement constater que, même si le droit des assurances pose l’écrit comme preuve principale et la liberté comme preuve subsidiaire par opposition au droit commun qui pose la liberté comme principe et l’écrit comme exception, le droit commun en l’instant est plus assure mieux la sécurité des parties. Dans les assurances, l’exigence de l’écrit n’a qu’un rôle processuel en terme d’efficacité de la preuve, alors qu’en droit civil ou commercial, au-delà de l’efficacité processuelle, il est dans certains cas, une condition sine qua non de validité du contrat. Il serait judicieux pour le législateur CIMA de faire de l’écrit une condition de validité soit pour tous les contrats d’assurance, soit pour certains types de contrat, pour mieux garantir la sécurité juridique des parties, majoritairement l’assuré. Car l’absence de trace écrite crée un doute qui profite à l’assureur. Evidence in insurance, as in all areas of law, plays a decisive role in the outcome of a trial. Given the specific and complex nature of insurance law, one is entitled to ask whether the legal framework for evidence in insurance truly differs from that of general law in order to better protect the parties. This study simply observes that, even though insurance law establishes written evidence as the primary form of proof and freedom of expression as secondary evidence, in contrast to general law which establishes freedom of expression as the principle and written evidence as the exception, general law currently provides greater security for the parties. In insurance, the requirement for a written document serves only a procedural purpose in terms of evidentiary effectiveness, whereas in civil and commercial law, beyond procedural efficiency, it is, in some cases, a prerequisite for the validity of the contract. It would be wise for the CIMA legislator to make a written document a condition of validity, either for all insurance contracts or for certain types of contracts, to better guarantee the legal security of the parties, primarily the insured. The absence of a written record creates doubt that benefits the insurer.
Keywords: Assurances dommages; CIMA; Common law; Contrat d’assurance; Droit commun; Evidence; Insurance contract; Preuve; Property and casualty insurance

La saisie du bétail à l’aune de la réforme de l’Acte Uniforme portant Organisation des Procédures Simplifiées de Recouvrement et des Voies d’Exécution - Nguiyan Fils, Dieu Le Fit (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
La saisie du bétail s’entend traditionnellement comme l’opération permettant au débiteur muni d’un titre exécutoire et sans commandement préalable de mettre sous-main de justice le bétail de son débiteur en vue de se l’attribuer ou de le vendre et se faire payer sur le prix. Cette définition permet de se faire une idée sur la nouvelle mesure d’exécution du législateur communautaire. Toutefois, l’analyse ne se contente pas de cette évidence. Elle cherche à dégager la conception tant juridique que judiciaire dans la réforme des voies d’exécution. Deux tendances se dégagent : Le visage d’une part et le virage d’autre part dans les dispositions particulières à la saisie du bétail. The seizure of livestock is traditionally understood as the operation allowing the debtor provided with an enforceable title and without prior command to take the livestock of his debtor under judicial control with a view to attributing it to himself or to selling it and charge on the price. This definition allows us to get an idea of the new implementing measure from the Community legislator. However, the analysis is not satisfied with this evidence. It seeks to identify both the legal and judicial conception in the reform of the means of execution. Two trends emerge: The face on the one hand and the shift on the other hand in the specific provisions for the seizure of livestock.
Keywords: Bétail; Livestock; Means of exécution; Reform; Réforme; Saisie; Seizure; Voies d’exécution

L’intime conviction du juge dans la prise des décisions en cas d’une victime catalyseuse - Siro Gimiko, Ghislain (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Le rôle actif du juge en matière pénale a pour but de reconstituer la scène pour déterminer si la défense, fut-elle avec des conséquences très grave, se justifie et s’il y a lieu d’en établir la proportionnalité. Le juge doit marcher dans ces voies en demeurant actif, en garantissant le respect des droits de la défense et du contradictoire. D’aucun savent que la justice est rendue par des hommes qui jugent d’autres hommes. Chacun sait, chacun sent qu’il s’agit là d’une mission impossible, voilà pourquoi, le juge doit faire preuve de ce souci d’humanité en demeurant actif. Du reste, la personne qui riposte une attaque doit encore savoir que l’agression doit être quasiment contemporaine de la réaction, se situer en instance de raison avant cette dernière, être en somme quasiment actuelle par rapport à la riposte. Il y a lieu de dire que la riposte est un plat qui se mange chaud. Si l’attaque est déjà passée, il n’y a plus lieu d’évoquer sa défense, car c’est une pure vengeance ; et si l’attaque n’est qu’éventuelle, résultant par exemple d’une menace, celui qui se ferait justice préventivement bénéficierait peut être de la mansuétude du juge au titre de la peur, mais ne serait pas justifié. Il faut donc un danger certain, mais cette certitude n’implique pas nécessairement que la personne se soit trouvée en péril de mort. The active role of the judge in criminal matters aims to reconstruct the scene in order to determine whether the defendant with very serious outcome is justified and if there is a way of establishing an equitability in the case. The judge must follow these paths by remaining active, guaranteeing respect for the rights of the defense and all the contradictories. It is well known to all that the justice system is managed by men judging other men. And everyone knows and feels, that it is an impossible task; therefore, the judge must show the concern for humanity by remaining active. Lastly, the person responding to an attack should know and understand that the aggression and reaction must relatively be done at the same time, in short, the cause or reasons must preced almost immediate in relation to the response. It is said that retaliation is a dish best eaten when it is still hot. If the attack has already occurred, there is no point in instigate it as self-defense, because it is a pure revenge; and however if the attack is eventual results from, i.e. from a threat, then the person who took the defensive justice might benefit from the judge's mercy or compassion, as fear is raised as an excuse for the act, however would not justified the act. Therefore, there is a conclusive danger, but this certainty does not necessarily imply weather the person was already in a life or death situation.
Keywords: Appréciation souveraine; Catalyst victim; Controversial debate; Decision making; Droit de la défense; Débat contradictoire; Intimate conviction; Intime conviction; Judge; Juge; Prise de décision; Right of the defense; Sovereign assessment; Victime catalyseuse

Le cumul des responsabilités contractuelle et extracontractuelle en droit burkinabè - Somda, Nibéhen Isidore; Nombre, Grihobou Roland (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2026)
L’article analyse le cumul des responsabilités contractuelle et extracontractuelle en droit positif burkinabè. En effet, la jurisprudence a consacré depuis fort longtemps le principe de non-cumul, mieux nommé de non option des responsabilités. Il se pose alors la question des éléments constitutifs du cumul et des sanctions applicables en cas de violation du principe ainsi posé. Il ressort que le cumul suppose un droit d’option du créancier en faveur des règles des articles 1382 et suivants du code civil pour bénéficier de la réparation des dommages issus de la violation, par le débiteur, de ses obligations contractuelles. De la jurisprudence des juridictions du fond, le cumul s’appréhende comme un mélange ou panachage des règles délictuelles et des règles contractuelles ou une concurrence des deux. Quant à la sanction applicable, elle se caractérise par une imprécision saisissante en ce qu’en cas de violation de la règle, les juridictions l’apprécient tantôt, comme une règle de procédure, tantôt comme une règle de fond. This article analyzes double civil liability in contract and tort in burkinabe law. By precedent, liability in tort and contract are not cumulative, as a matter of principle. Cumulative liability presupposes that the creditor opted for compensatory damages in accordance with Article 1382 and subsequent provisions of the civil code in case of a breach of contract by the debtor. In lower-court rulings, double civil liability describes either competing liability rules in tort and contract or a mixture of such rules. The applicable sanction against violations of the non-cumulative liability rule remains unclear as the rule is both characterized by courts either as procedural or substantive.
Keywords: Cumul; Jurisprudence; Non-cumul; Responsabilité contractuelle; Responsabilité extracontractuelle

L’article 54 de la charte de la refondation : vers une refondation de la procédure pénale nigérienne - Abarchi, Djibril Balkissa (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Au lendemain du coup d’Etat du 26 juillet 2023, la politique dite de « refondation nationale » a donné lieu à l’adoption d’une charte de la refondation faisant l’option pour la mise en œuvre de certaines valeurs essentielles dans la conduite des affaires publiques. Dans la foulée des innovations à promouvoir, la charte de la refondation prescrit en son article 54 le droit et l’obligation de tout citoyen de saisir le parquet pour dénoncer ou porter plainte en cas de détournement de deniers publics, d’enrichissement illicite, de corruption et de népotisme. Reconnaître de telles prérogatives à tous est assurément une innovation qui déroge à plusieurs égards à la procédure pénale classique. En attendant l’intervention de dispositions législatives pour apporter des précisions sur les conditions de mise en œuvre de ce qui est pour l’heure une annonce d’un principe d’implication des citoyens dans la procédure pénale aux fins de participation à la moralisation de la vie publique, il est permis de procéder à une analyse mettant en exergue la portée juridique de cette innovation. In the aftermath of the coup d'état of July 26, 2023, the so-called "national refoundation" policy led to the adoption of a charter of refoundation making the option for the implementation of certain essential values in the conduct of public affairs. In the wake of the innovations to be promoted, the charter of the refoundation prescribes in its article 54 the right and obligation of every citizen to refer the matter to the public prosecutor's office to denounce or file a complaint in the event of embezzlement of public funds, illicit enrichment, corruption and nepotism. Recognizing such prerogatives for all is certainly an innovation that derogates in several respects from traditional criminal procedure. Pending the intervention of legislative provisions to provide clarification on the conditions for the implementation of what is for the moment an announcement of a principle of involvement of citizens in criminal proceedings for the purpose of participating in the moralization of public life, it is permissible to carry out an analysis highlighting the legal scope of this innovation.
Keywords: Charte; Charter; Complaint; Criminal procedure; Denunciation; Dénonciation; Niger; Plainte; Procédure pénale; Refondation; Refoundation

Quelques limites du droit des sociétés OHADA - Adoku, Kankue Daniel (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Le droit des sociétés constitue un archétype du droit gestionnaire, une technique d’organisation de l’entreprise. Ainsi, ce droit occupe-t-il une place importante au sein du monde des affaires. L’œuvre communautaire d’harmonisation du droit des affaires entrepris par le droit OHADA n’a pas manqué de prendre en compte ce droit. Seulement, cette œuvre communautaire, ne postulant pas à la perfection, affiche en effet un certain nombre de limites. D’une part, devant l’évolution du droit de sociétés, l’OHADA s’est recroquevillé sur elle-même, n’intégrant nullement les impératifs nouveaux du droit des sociétés. D’autre part, ce droit souffre d’une certaine ineffectivité dans son articulation avec les règles produites par certaines organisations communautaires concurrentes existant dans la zone de sa compétence territoriale. Corporate law is archetype of managerial law. Corporate law is also a technique used to organise the business. So, corporate law is very important in the business world. However, the harmonisation of corporate law by OHADA reveals several limitations. Corporate social responsability does not exist in OHADA law. In his articulation with the law of others community organizations, OHADA law sometimes does not produce any effect.
Keywords: Compliance; Comply or explian; Corporate governance; Droit OHADA; Droit UMOA; Droit souple; OHADA law; Soft law; UMOA law

Les droits et libertés menacés par la législation sur la cybercriminalité et l’interception de sécurité au Niger - Alassane Barmo, Chamsoudini (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
La présente contribution consiste à analyser les atteintes étatiques à certains droits et libertés fondamentaux dans le cadre de la lutte contre certaines infractions graves. Pour ce faire, il importe, d’abord, de chercher à identifier les dispositions des textes portant sur l’interception des communications électroniques et sur la répression de la cybercriminalité menaçant le droit au respect à la vie privée, au secret des correspondances dématérialisées et la liberté de pensée, d’opinion, d’expression et de presse. Ensuite, une fois ces dispositions identifiées, il sera question, dans une démarche prospective, d’envisager les mécanismes juridiques renforçant la protection de ces droits et libertés fondamentaux. This contribution consists of analyzing state infringements on certain fundamental rights and freedoms in the context of the fight against certain serious offences. In order to do so, it is important, first of all, to identify the provisions of the laws on the interception of electronic communications and on the repression of cybercrime that threaten the right to privacy and freedom of expression of citizens. Then, once these provisions are identified, it will be a question of trying to make them conform to the respect of fundamental rights and freedoms.
Keywords: Cybercrime; Cybercriminalité; Droits fondamentaux; Fundamental rights; Interceptions de sécurité; Niger; Security intercepts

La mise à disposition illicite de main-d’œuvre en droit togolais - Alipoe, Pierre-Paul Kossi (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
La mise à disposition de main-d’œuvre occupe une place croissante dans l’organisation contemporaine du travail, sous l’effet conjugué des exigences de flexibilité économique et de rationalisation des coûts. En droit togolais, cette pratique fait l’objet d’un encadrement rigoureux destiné à prévenir les dérives liées à l’exploitation de la force de travail et au contournement des normes protectrices du salarié. Le régime juridique applicable met en évidence les fondements et la portée des incriminations de prêt illicite de main-d’œuvre et de marchandage, à travers l’identification des critères de qualification retenus par le droit positif. L’analyse fait apparaître le rôle central du but lucratif et du préjudice dans la caractérisation de l’illicéité, ainsi que l’importance des montages tripartites dans l’appréciation des situations litigieuses. Ces mécanismes répressifs poursuivent une double finalité : assurer la protection effective des travailleurs et préserver une concurrence loyale entre les entreprises. L’ensemble révèle enfin le rôle structurant de l’interprétation jurisprudentielle dans la délimitation du licite et de l’illicite, au croisement des impératifs économiques et des exigences sociales. The supply of labour has become an increasingly significant feature of contemporary work organisation, driven by the combined demands of economic flexibility and cost rationalisation. Under Togolese law, this practice is subject to strict regulation aimed at preventing abuses related to the exploitation of labour and the circumvention of employee-protective rules. The applicable legal framework highlights the foundations and scope of the offences of unlawful labour supply and labour broking, through the identification of the qualifying criteria established by positive law. Particular emphasis is placed on the central role of profit motive and harm in determining illegality, as well as on the relevance of tripartite arrangements in assessing disputed situations. These repressive mechanisms pursue a dual objective: ensuring effective protection of workers and safeguarding fair competition between undertakings. Overall, the analysis underscores the structuring role of judicial interpretation in delineating lawful and unlawful practices, at the intersection of economic imperatives and social requirements.
Keywords: Droit du travail togolais; Employment flexibility; Flexibilité de l’emploi; Labour broking; Main-d’œuvre; Marchandage; Mise à disposition; Protection des travailleurs; Prêt illicite de main-d’œuvre; Supply of labour; Togolese labour law; Unlawful labour supply; Worker protection

La saisie conservatoire des bétails en droit OHADA - Assogba, Lucien (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2026)
« L’opposabilité, depuis le 14 février 2024, du nouvel AUPSRVE consacre une avancée substantielle avec l’émergence d’une procédure d’indisponibilité spécifique au cheptel. En autorisant cette mesure conservatoire sur un patrimoine vivant essentiel, le législateur communautaire renforce l’efficacité du droit de suite du créancier, lui permettant de pallier le péril dans le recouvrement avant même l’obtention d’une force exécutoire au fond. » L’article analyse ce régime singulier, dont la spécificité se justifie par la nature de l’objet saisi et les réalités du milieu. Le bétail, défini comme l’ensemble des animaux élevés ayant une valeur marchande (y compris ceux en transhumance), est clairement distingué des animaux de compagnie, qui restent insaisissables. Le régime est fortement inspiré du droit commun des saisies mobilières. Les prérequis classiques sont maintenus : la créance doit « paraître fondée en son principe » et l’urgence doit être justifiée. Cependant, la mobilité intrinsèque du bétail dans le cadre de la transhumance est considérée comme un péril imminent suffisant pour justifier la saisie conservatoire. Bien que le débiteur conserve l’usage de l’animal saisi, celui-ci devient indisponible. L’huissier de justice ou l’autorité en charge de la saisie conservatoire joue un rôle crucial en pouvant ordonner la remise des animaux à un séquestre désigné. Cette mesure vise à garantir le bien-être du bétail et à préserver sa valeur économique, compte tenu de sa nature vivante et périssable. La réforme, bien que moderne, se heurte aux réalités coutumières africaines. Le bétail est souvent perçu comme un symbole de richesse et peut faire l’objet de propriété communautaire ou clanique, ce qui rend l’identification du débiteur individuel et l’assiette de la saisie extrêmement complexe. “The enforceability, since February 14, 2024, of the new AUPSRVE represents a substantial advancement with the emergence of a specific unavailability procedure for livestock. By authorizing this precautionary measure on a vital living asset, the EU legislator strengthens the effectiveness of the creditor’s right of pursuit, allowing them to address the risk in recovery even before obtaining an enforceable decision on the merits.” The article analyzes this unique regime, whose specificity is justified by the nature of the object seized and the realities of the field. Livestock, defined as all raised animals with market value (including those in transhumance), is clearly distinguished from pets, which remain exempt from seizure. The regime is heavily inspired by the general law on movable property seizures. The usual prerequisites are maintained: the claim must “appear to be well-founded in principle” and urgency must be justified. However, the intrinsic mobility.
Keywords: AUPSRVE; Bétail; Livestock; Precautionary seizure; Saisie conservatoire; Saisie-vente; Seizure-sale

La mise en oeuvre d'une stratégie de la responsabilité sociale des entreprises au sein des organisations - Bah, Elhadj Oumar (Université du Québec à Montréal, 2026)
Ce mémoire explore la question de la mise en oeuvre de la responsabilité sociale des entreprises (RSE) en proposant une stratégie intégrée fondée sur une revue narrative de la littérature scientifique. L'analyse démontre que la RSE a évolué d'un concept moral à un cadre réglementaire et stratégique global, articulé autour de ses dimensions économiques, sociales et environnementales. La recherche révèle un manque d'approches méthodologiques complètes dans la littérature, ce qui justifie la pertinence de cette étude. En synthétisant les travaux de plusieurs auteurs, une stratégie de mise en oeuvre en huit étapes est proposée : désignation d'un responsable, identification des parties prenantes, diagnostic RSE, élaboration d'une politique, formation, mise en oeuvre d'actions concrètes, communication intégrée, et évaluation continue. Cette stratégie vise à offrir un cadre structuré et adaptatif pour les organisations souhaitant intégrer efficacement la RSE dans leur gouvernance et leurs opérations, en s'appuyant sur des référentiels normatifs, tels que l'ISO 26000 et le GRI. This thesis explores the implementation of corporate social responsibility (CSR) by proposing an integrated strategy based on a narrative review of the scientific literature. The analysis shows that CSR has evolved from a moral concept to a global regulatory and strategic framework, articulated around its economic, social, and environmental dimensions. The research reveals a lack of comprehensive methodological approaches in the literature, which justifies the relevance of this study. By synthesizing the work of several authors, an eight-step implementation strategy is proposed: appointing a CSR manager, identifying stakeholders, conducting a CSR diagnosis, developing a CSR policy, providing training, implementing concrete actions, integrated communication, and continuous evaluation. This strategy aims to provide a structured and adaptive framework for organizations wishing to effectively integrate CSR into their governance and operations, based on normative frameworks such as ISO 26000 and GRI.
Keywords: CSR; Corporate Social Responsibility; Développement durable; Gouvernance; Governance; Implementation; Mise en œuvre; Parties prenantes; RSE; Responsabilité sociale des entreprises; Stakeholders; Strategy; Stratégie; Sustainable development

La rhétorique des droits humains dans le débat sur la dérogation à certaines dispositions de l’accord sur les ADPIC proposée à l’OMC lors de la pandémie de COVID-19 - Bahary, Emmanuelle (Université du Québec à Montréal, 2026)
Ce mémoire est une analyse argumentative des discours présentés à l’OMC en faveur et en défaveur de la Dérogation proposée le 2 octobre 2020 par l’Inde et l’Afrique du Sud. Cette dernière avait comme objectif de suspendre pour la durée de la pandémie de COVID-19 certaines dispositions de l’Accord sur les ADPIC pour préserver la santé publique et remédier à l’iniquité vaccinale. Elle se base sur l’idée controversée selon laquelle l’Accord interfère avec un accès abordable et équitable aux produits de santé à l’échelle mondiale. Le cadre théorique utilisé servira à conceptualiser une rhétorique des droits humains, un modèle argumentatif reposant sur l’instrumentalisation à des fins de justification de politiques économiques. Ce modèle argumentatif a la particularité d’utiliser l’indétermination du droit, des droits humains et de la technique pour formuler de multiples réponses contradictoires simultanéement valides, ainsi que la prétention à l’objectivité de l’aspect formel du droit, fondamental des droits humains et scientifique de la technique pour aparaître apolitique et non-arbirtaire. En recadrant ces discours dans le modèle proposé, nous verrons que l’instrumentalisation des droits humains contient plusieurs problèmes, notamment la légitimation d’arguments opposés pouvant autant être destinés à la réalisation du droit qu’à la défense d’intérêts entrant en conflit avec son objet. This memoir is an argumentative analysis of the narratives presented at the WTO in favor or against the Derogation submitted by India and South Africa on October 2nd, 2020. The latter aimed to suspend some of the WTO TRIPS Agreement dispositions for the duration of the COVID-19 pandemic to preserve public health as well as serving as a remedy to vaccinal inequity. It is based on the controversed idea that the Agreement interferes with an abordable and equitable access to health products at a global scale. The theoretical framework will contribute to conceptualize a human rights rhetoric, an argumentative model based on the instrumentalization of human rights to justify economic policies. This argumentative model uses law, human rights and technical indeterminacy to formulate multiple simultaneously valid contradictory answers, and the claim to objectivity of the formal aspect of the law, the fundamental aspect of human rights and the scientific aspect of expertise to seem non-political and non arbitrary. By reframing these narratives in the proposed model, we’ll see that human righs instrumentalization is problematic at multiple levels, notbly the legitimation of opposed arguments that can destined as much to the law’s realization as to the promotion of interests that are at odds with its object.
Keywords: Analyse discursive; Approches critiques; Argumentative analysis; Critical approaches; Droits humains; Human rights; Human rights rhetoric; Intellectual property; Propriété intellectuelle; Rhétorique des droits humains

Le créancier face aux personnes morales de droit public dans l’espace OHADA; statu quo ou évolution ? : une analyse de la protection des créanciers à l’aune du nouvel acte uniforme relatif aux procédures simplifiées de recouvrement et voies d’exécution - Balogog, Eunice Pauline (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Le créancier qui entame les voies d’exécution instituées par les États de l’OHADA en vue du recouvrement de sa créance est exposé au risque d’inexécution du titre exécutoire, surtout dans le contentieux qui touche les personnes morales de droit public. En tant que bénéficiaires de l’immunité d’exécution, la procédure leur est en effet inapplicable, causant ainsi d’énormes difficultés aux créanciers, notamment en mettant en péril le crédit et l’investissement. Avec la réforme survenue récemment, il était nécessaire de s’interroger sur la prise en compte de toutes ces difficultés par le nouvel Acte uniforme portant organisation des procédures simplifiées de recouvrement et des voies d’exécution (AUPSRVE), entré en vigueur le 16 février 2024. L’étude compare à cette fin les dispositions du nouvel Acte uniforme avec celles de l’ancien texte et la pratique en la matière, avec pour objectif d’apprécier l’environnement juridique actuel en matière de protection des créanciers des personnes morales de droit public au moment du recouvrement de leurs créances. Cette analyse comparative permet de mettre en évidence, l’évolution notable du droit, qui va dans le sens du renforcement des intérêts des créanciers, quoique insuffisante. The creditor who initiates the enforcement procedures established within the OHADA Member States for the recovery of his claim is exposed to the risk of non-execution of the enforceable title, particularly in disputes involving public law legal persons. As beneficiaries of execution immunity, such entities are in practice shielded from enforcement measures, thereby creating significant difficulties for creditors, notably by jeopardizing credit and investment. In light of the recent reform, it has become necessary to question the extent to which these difficulties are addressed by the new Uniform Act organizing simplified recovery procedures and enforcement measures (AUPSRVE), which entered into force on 16 February 2024. This study therefore compares the provisions of the new Uniform Act with those of the former text and with existing practice, with the aim of assessing the current legal framework governing the protection of creditors of public law legal persons in the recovery of their claims. This comparative analysis highlights a notable evolution of the law in favor of strengthening creditors’ interests, albeit in an insufficient manner.
Keywords: Creditor; Créancier; Debt recovery; Personnes morales de droit public; Public law legal persons; Recouvrement

L’appréhension du lien contractuel du Code des obligations civiles et commerciales (COCC) du Sénégal - Diawara, Moussa (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Le lien de droit, en tant qu’accrochage, donne toute la quintessence du lien contractuel du COCC. Ce dernier, lorsque celui-là est appréhendé comme altérité, étale son incomplétude au profit d’autres branches du droit. Par ailleurs, les obligations que le lien contractuel du COCC fait naître peuvent, inversement, rétroagir sur lui afin d’en éclairer ou d’en assurer le sens. C’est cette thèse que cet article étaie. The legal relationship, as a form of connection, embodies the quintessence of the contractual relationship of the COCC. The latter, when understood as otherness, exposes its incompleteness to the benefit of other branches of law. Moreover, the obligations of the COCC that the contractual relationship creates can, conversely, retroact on it in order to clarify or ensure its meaning. This is the thesis that this article supports.
Keywords: COCC; Contract; Contractual relationship; Contrat; Lien contractuel; Obligation; Sénégal

Le contrat, un instrument juridique ou un « pilier du droit » ? - Gueukam Tchako, Yannick (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Plus de deux siècles de son adoption (1804 à nos jours), les dispositions du Code civil applicable au Cameroun portant sur le droit commun du contrat sont jugées vétustes. Elles méritent de reformes, au nom de la doctrine de l’attractivité et de la performance économique, dans un contexte politique d’africanisation du droit des contrats et de la concurrence accrue du droit de la vente internationale. D’un regard panoramique, la présente analyse, livre un aperçu en profondeur du « contrat, un instrument juridique ou un pilier du droit » ? Il en ressort de cette contribution que le contrat est à la fois un instrument juridique et un « pilier du droit ». En tant qu’instrument juridique extrêmement performant, il vise à offrir un instrument permettant la plus grande liberté économique possible, ouverte à l’imagination des individus, tout en veillant scrupuleusement à éviter les déséquilibres économiques et en protégeant toutes les parties au contrat en tenant compte de leur particularité. More than two centuries after its adoption (1804 to the present day), the provisions of the Civil Code applicable in Cameroon concerning the common law of contract are considered outdated. They deserve reforms, in the name of the doctrine of attractiveness and economic performance, in a political context of Africanization of contract law and increased competition from international sales law. From a panoramic perspective, the present analysis provides an in depth overview of "the contract, a legal instrument or a pillar of law"? It emerges from this contribution that the contract is both a legal instrument and a "pillar of law." As an extremely efficient legal instrument, it aims to provide a tool that allows for the greatest possible economic freedom, open to the imagination of individuals, while meticulously ensuring the avoidance of economic imbalances and protecting all parties to the contract by taking their particularities into account.
Keywords: Accord de volonté; Agreement of will; Contract; Contrat; Economic performance; Imprévision; Legal certainty; Performance économique; Sécurité juridique; Unforeseen circumstances

L’efficacité de la réglementation des terrains inconstructibles en droit de l’urbanisme au Cameroun - Léganlé, Gervais (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Avec la loi du 21 avril 2004 régissant l’urbanisme au Cameroun et les Décrets subséquents du 23 avril 2008 notamment, la réglementation des terrains inconstructibles en droit de l’urbanisme, dont l’efficacité est questionnée, vise tant à dissuader les personnes qui s’obstinent à construire sur des parcelles interdites à la construction, qu’à protéger particulièrement leur vie. Et eu égard à l’incivisme et à l’insouciance de certains, la présente analyse soulève l’épineuse préoccupation du rapport de force entre la rigueur des prescriptions urbanistiques relatives aux terrains inconstructibles et leur respect scrupuleux sur toute l’étendue du territoire national. Assurément, la détermination expresse des sols impropres à la construction assortie des sanctions rigoureuses, atteste de ce que les règles d’urbanisme encadrant les terrains inconstructibles sont d’une efficacité voulue par le législateur. Malheureusement, des obstacles tels que les constructions anarchiques et l’échec de la répression, qui entravent l’application de ces dispositions, témoignent plutôt d’une efficacité rudement mise à l’épreuve. With the law of April 21, 2004 governing urban planning in Cameroon and the subsequent decrees of April 23, 2008 in particular, the regulation of unconstructible land in urban planning law, whose effectiveness is questioned, aims both to dissuade people who persist in building on plots prohibited for construction, and especially to protect their life. And in view of the incivility and carelessness of some, this analysis raises the thorny concern about the balance of power between the rigor of urban planning regulations regarding unconstructible land and their scrupulous observance throughout the national territory. Certainly, the express determination of soils unsuitable for construction and the rigorous penalties attest to the fact that the planning rules governing non-constructible lands are effective as intended by the legislator. Unfortunately, obstacles such as anarchic constructions and the failure of repression, which hinder the application of these provisions, testify rather to a harshly tested effectiveness.
Keywords: Droit de l’urbanisme; Efficacité; Efficiency; Regulation; Réglementation; Terrains inconstructibles; Unconstructible land; Urban planning law

OMC DS611 : Limiter l’extraterritorialité judiciaire en propriété intellectuelle - Moudjahidi, Abdoulbastoi (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
La politique chinoise d’injonctions antipoursuites (IAP) dans les litiges liés aux brevets essentiels à une norme (BEN) et aux conditions FRAND viole l’Accord sur les ADPIC. Les arbitres de l’OMC ont établi une doctrine de « non-frustration » en vertu de l’article 1:1, affirmant que les mesures nationales ne peuvent pas nuire aux systèmes de propriété intellectuelle (PI) des autres membres. Les IAP chinoises, assorties de lourdes amendes journalières, restreignent indûment les droits des titulaires de brevets en entravant l’application des droits à l’étranger et en faussant les négociations de licences mondiales. La Chine doit désormais réviser sa politique pour garantir la conformité et une transparence accrue pour les « affaires types ». Cette décision limite les effets extraterritoriaux des mesures judiciaires, favorisant une approche plus équilibrée des litiges transfrontaliers en matière de PI. China's Anti-Suit Injunction (ASI) policy in SEP/FRAND disputes violates the TRIPS Agreement. The WTO arbitrators established a "non-frustration" doctrine under Article 1:1, holding that national measures cannot undermine other Members' IP systems. Chinese ASIs, with high daily fines, unduly restrict patentees' rights (Arts. 2 :1 & 2 :2) by obstructing enforcement abroad and distorting global license negotiations. China must now revise the policy to ensure compliance and greater transparency (Art. 6 :1) for influential "type cases". This decision limits the extraterritorial effects of judicial measures, fostering a more balanced approach to cross-border IP litigation.
Keywords: Brevet; Intellectual property; Propriedad intelectual; Propriété intellectuelle

La nationalité burkinabè dans le nouveau code des personnes et de la famille - Nombre, Grihobou Roland (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2026)
Le Code des personnes et de la famille (CPF) burkinabè de 1989 a récemment fait l’objet d’une modification le 1er septembre 2025. Parmi les matières objet de la modification figure la nationalité burkinabè. Cet article s’attache à déterminer la mesure dans laquelle le droit de la nationalité burkinabè a évolué du fait de cette révision du CPF de 1989. Il relève que cette nationalité reformée se caractérise, d’une part, par un durcissement de l’accès et de la privation de la nationalité burkinabè. Aussi, des ambiguïtés et incohérences de certaines dispositions réaménagées sur la nationalité sont-elles décelées dans le nouveau code, rendant ainsi incertain la portée juridique de ces dispositions. D’autre part, le droit de la nationalité burkinabè est désormais plus protecteur de l’étranger apatride ou encore résident permanent qui bénéficient, l’un et l’autre, d’un statut juridique leur conférant la jouissance spécifique de certains droits. Burkina Faso 1989 Family Code was just amended on September 1, 2025. Among the issues within the scope of the revised Code lies the burkinabe nationality. This article inquires about how the burkinabe nationality law evolved under the revised Code. On the one hand, it finds that the revision was restrictive of access to nationality and made deprivation of nationality more severe. Also, some highlighted inconsistencies in the provisions of the revised Family Code on nationality cause uncertainty as to their meaning and legal force. On the other hand, the revision achieved more protection for foreigners, whether stateless or permanent resident, by establishing a legal status for the stateless and the permanent resident, thereby granting them more rights than they had under the 1989 Code.

Le mariage coutumier à l’aune de la loi n°2024/016 portant organisation du système d’enregistrement des faits d’état civil au Cameroun - Tafon, Arouna (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
En tant qu’institution traditionnelle profondément ancrée dans les pratiques culturelles, le mariage coutumier occupe une place centrale dans l’organisation sociale camerounaise. Jadis cantonné à une reconnaissance juridique restreinte au sein du droit positif, il connait aujourd’hui une transformation juridique majeure, sous l’impulsion de la loi n°2024/016 du 2 juillet 2024 portant organisation du système d’enregistrement des faits d’état civil au Cameroun. En fixant les modalités procédurales de transcription, cette loi consacre par-là la transcription du mariage coutumier comme un mécanisme essentiel de sa reconnaissance et de son efficacité juridique. La transcription apparait ainsi comme une condition déterminante de la validité légale du mariage coutumier en ce qu’elle permet son intégration dans l’ordre juridique étatique. As a traditional institution deeply rooted in cultural practices, customary marriage occupies a central place in Cameroonian social organization. Once relegated to limited legal recognition within positive law, it is now undergoing a major legal transformation, driven by Law N°2024/016 of July 23, 2024, concerning the organization of the civil registration system in Cameroon. By establishing the procedural requirements for transcription, this law enshrines the transcription of customary marriage as an essential mechanism for its recognition and legal validity. Transcription thus appears as a determining condition for the legal validity of customary marriage, as it allows for its integration into the state legal order.
Keywords: Civil status records; Customary marriage; Faits d’état civil; Mariage coutumier; Transcription

La protection de la vie privée face au caractère international du numérique - Tchenti, Ismaël (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
A l’ère du numérique, les données personnelles circulent librement au-delà des frontières, échappant souvent au contrôle des Etats. Le droit béninois, bien qu’enrichi par le code du numérique et l’action de l’APDP, se heurte à des limites structurelles lorsqu’il s’agit de protéger efficacement la vie privée face à des traitements transnationaux opérés par des acteurs étrangers. En effet, le droit béninois, dans sa configuration actuelle, ne permet pas une protection pleinement efficace de la vie privée face aux enjeux transfrontaliers du numérique, en raison de l’absence de mécanismes extraterritoriaux et de coopération internationale suffisants. Ainsi, une convergence normative avec les standards internationaux comme le RGPD et le renforcement des capacités de l’APDP pourraient améliorer la résilience du droit béninois face aux défis du numérique. Ainsi, la protection de la vie privée face au caractère international du numérique est un enjeu important au Bénin, qui nécessite une approche coordonnée et des solutions technologiques, réglementaires et éducatives. In the digital age, personal data circulates freely across borders, often escaping state control. Beninese law, although enriched by the Digital Code and the work of the APDP (National Agency for the Protection of Personal Data), faces structural limitations when it comes to effectively protecting privacy against transnational data processing carried out by foreign actors. Indeed, Beninese law, in its current form, does not allow for fully effective protection of privacy in the face of the transnational challenges of the digital age, due to the lack of sufficient extraterritorial mechanisms and international cooperation. Thus, normative convergence with international standards such as the GDPR and strengthening the capacities of the APDP could improve the resilience of Beninese law in the face of digital challenges. Thus, protecting privacy in the face of the international nature of digital technology is a significant challenge in Benin, requiring a coordinated approach and technological, regulatory, and educational solutions.
Keywords: Données personnelles; Droit international; Globalization; International law; Mondialisation; Personal data; Privacy; Protection; Vie privée

La consolidation du cadre normatif et institutionnel des TIC au Cameroun : Enjeux et perspectives pour une justice pénale moderne - Tepi, Samuel (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Les technologies de l’information et de la communication (TIC) en droit pénal camerounais retiennent désormais toute l’attention en raison de leur omniprésence et de leur évolution constante. Il est donc impératif de mettre en place un cadre normatif et institutionnel solide, prenant en compte toutes les variables, notamment nationales, internationales, institutionnelles et financières, afin d’assurer une justice pénale numérique efficace et durable. À cet égard, le Cameroun, au-delà de son dispositif normatif national et des institutions mises en place pour réguler et contrôler l’usage des TIC, s’est également engagé au plan international. Cependant, ces efforts restent insuffisants, d’où la nécessité de renforcer l’architecture institutionnelle et la gouvernance numérique du pays. Information and communication technologies (ICT) in Cameroonian criminal law now attract significant attention due to their omnipresence and constantly evolving nature. It is therefore essential to establish a robust normative and institutional framework that considers all variables— national, international, institutional, and financial—in a strengthened manner to achieve an effective and sustainable digital criminal justice system in Cameroon. To this end, beyond its national legal framework and regulatory institutions, Cameroon is also committed at the international level. Nevertheless, these efforts remain insufficient, highlighting the need to strengthen the country’s institutional architecture and digital governance.
Keywords: Adaptation; Cameroun; Criminal justice; Digital justice; Harmonisation; Harmonization; ICT; Justice numérique; Justice pénale; Renforcement; Strengthening; Sustainability; TIC; Viabilité

La pertinence de la contribution normative de la ZLECAF à la floraison des PME camerounaises - Zanga Etoundi, Antoinette Carine (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Cette réflexion sur la contribution normative de la ZLECAF à la floraison des PME au Cameroun a pu être établie d’une part en prenant en compte la pertinence avérée et effective de la contribution de la ZLECAF à l’épanouissement des PME. En mobilisant la méthode juridique et d’autres complémentaires (historique et comparative), il s’est agi de mettre en exergue le rôle de cette institution dans la redéfinition du cadre juridique du libre-échange en Afrique. L’établissement et la régulation des échanges libres entre les Etats parties à l’accord, sonne comme une nouveauté à travers la contextualisation qui en découle. La prise en compte des spécificités africaines dans le commerce interétatique se positionne comme une cure de jouvence à la bonne marche du commerce international africain. Il s’est également agi de faire valoir le redimensionnement de la contribution du genre dans le monde de l’entrepreneuriat en Afrique et particulièrement au Cameroun. L’accord stipule un nécessaire équilibre des genres en la matière, renforçant ce faisant la vocation des PME à être plus productives et mieux intégrantes. This reflection on the normative contribution of the AfCFTA to the flourishing of SMEs in Cameroon was established, firstly, by considering the proven and effective relevance of the AfCFTA's contribution to SME development. By employing legal methods and other complementary approaches (historical and comparative), the aim was to highlight the role of this institution in redefining the legal framework of free trade in Africa. The establishment and regulation of free trade between the States Parties to the agreement is a novelty, given the resulting contextualization. Taking into account African specificities in interstate trade is seen as a revitalization of the smooth functioning of African international trade. It was also important to emphasize the increased role of gender in the world of entrepreneurship in Africa, and particularly in Cameroon. The agreement stipulates a necessary gender balance in this area, thereby reinforcing the role of SMEs in becoming more productive and more inclusive.
Keywords: AfCFTA; Contribution normative; Echanges inter étatiques; Entreprenariat féminin; Intergovernmental trade; Normative contribution; PME; SME; Women's entrepreneurship; ZLECAf

L’adage « nul n’est censé ignorer la loi » et la théorie juridique de l’information - Zourmba, Moustapha (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
L’adage « nul n’est censé ignorer la loi » constitue l’un des fondements classiques de l’ordre juridique moderne. Hérité du droit romain (ignorantia juris non excusat), il repose sur une présomption selon laquelle toute personne soumise à la loi est réputée en avoir connaissance. Cette fiction juridique vise avant tout à garantir la sécurité juridique, l’égalité devant la loi et l’effectivité des normes juridiques, en empêchant que l’ignorance réelle ou prétendue du droit ne devienne un moyen systématique d’échapper à la responsabilité juridique. Toutefois, dans un contexte marqué par la technicité croissante du droit et la multiplication des sources juridiques ˗ nationales, régionales et internationales ˗cette présomption apparaît de plus en plus contestable. L’accessibilité et l’intelligibilité de la loi, pourtant consacrées comme exigences de l’État de droit, demeurent inégalement garanties, notamment dans les sociétés où le pluralisme juridique, les barrières linguistiques et les inégalités socio-économiques limitent l’accès effectif au droit. Ainsi, cette étude entend établir qu’à l’époque contemporaine, l’effectivité de l’adage « nul n’est censé ignorer la loi », à l’aune des exigences de la théorie juridique de l’information, commande la consécration d’obligations corrélatives à la charge de l’État et du citoyen. The adage “ignorance of the law is no excuse” constitutes one of the classic foundations of the modern legal order. Inherited from Roman law (ignorantia juris non excusat), it is based on a presumption according to which any person subject to the law is deemed to be aware of it. This legal fiction is primarily intended to ensure legal certainty, equality before the law, and the effectiveness of legal norms, by preventing actual or alleged ignorance of the law from becoming a systematic means of escaping legal responsibility. However, in a context marked by the growing technical complexity of the law, and the multiplication of legal sources ˗ national, regional, and international ˗ this presumption appears increasingly questionable. The accessibility and intelligibility of the law, although recognized as requirements of the rule of law, remain unevenly guaranteed, particularly in societies where legal pluralism, language barriers, and socio-economic inequalities limit effective access to the law. Thus, this study seeks to establish that, in the contemporary era, the effectiveness of the maxim “ignorance of the law is no excuse”, in light of the requirements of the legal theory of information, calls for the recognition of corresponding obligations incumbent upon both the State and the citizen.
Keywords: Adage; Citizen; Citoyen; Etat; Law; Loi; Obligations; State